Phenol hydrodeoxygenation and descriptor based on TM@Mo2C single-atom catalysts - Jiehang Wei; Shouqin Mu; Wenjuan Wang; Yuxin Xu; Mengjia Fu; Yingtao Liu; Xin Wang (Fuel, 2027)

Integrated analysis reveals the effects of substituting pea with mung bean on microbial succession and metabolite profiles during medium-temperature Daqu fermentation - Ruijuan Wang; Lijun Yan; Feng Ding; Hao Zhou; Boyang Xu; Shanshan Xu; Yuhan Yuan; Dongdong Mu; Xuefeng Wu; Xingjiang Li (International Journal of Food Microbiology, 2026)

Transformation of aflatoxins by a thermostable and mediator-independent laccase from Thermincola ferriacetica - Binbin Ouyang; Jiahao Gu; Wei Xu; Alexandra Rojkova; Ivan Zorov; Arkady Sinitsyn; Wanmeng Mu (Food Research International, 2026)

Triphasic sequential gas delivery via a photo-instructive hydrogel for enhanced diabetic skin wound healing - Jingwen Dong; Junjie Zhou; Shuguang Huang; Junmei Mu; Ye Tian; Zhifei Ding; Yihui Li; Aiping Wang; Zhanwei Zhou; Zeyu Xu; Minjie Sun (Chemical Engineering Journal, 2026)

Persulfate-assisted anaerobic digestion systems: advances in microbial electron transport chain reconstruction and metabolic regulation driven by reactive oxygen species - Yingjin Song; Sheng Xu; Yanshan Wang; Lan Mu; Huiling Niu; Qingyi Li; Yinjie Zhong; Yvxing Luo; Zhi Wang; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

A double-key responsive TDNs-HC/Cas13a DNA circuit for free-amplified detection and precise imaging of miRNAs in living cell - Shixiu Xiao; Yuying Liang; Yihan Zhang; Longjin Liang; Bin Xu; Xiaomei Mu; Shulin Zhao; Jianniao Tian (Analytica Chimica Acta, 2026)

Multi-response calibration and validation of a DEM for wet Mactra veneriformis–mudflat sediment mixtures during mechanised harvesting - Hangqi Li; Gang Mu; Bin Xu; Guangcong Chen; Guochen Zhang; Xiuchen Li (Biosystems Engineering, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Preparation and evaluation of silicate stabilized FeS nanoslurry for in-situ remediation of hexavalent chromium - Ning-Ning Xing; Hong-Ling Zhang; Pan-Pan Mu; Hui Jiang; Hong-Bin Xu (Chemical Engineering Journal, 2026)

Solar concentrated-light driven direct air capture with fast desorption kinetics using amine-modified monolithic composites - Fang Wang; Xuelin Xu; Zhonghai Zhang; Wendi Liu; Jinchi Mu; Jiandong Chen; Tao Wang (Chemical Engineering Journal, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Identification of the sex-linked region of the swimming crab Portunus trituberculatus - Haifu Wan; Sainan Ma; Shuohan Yang; Linran Zhang; Jishun Zhang; Pengxia Xu; Zelin Jiao; Shuai Guo; Shumei Mu; Xianjiang Kang (Aquaculture, 2026)

Neural and metabolic mechanisms of emetogenic foodborne toxins via the brain-gut axis in ageing and cachexia - Hao Xu; Muying Li; Yuting Liu; Guanghui Nie; Mu Li; Zitong Meng (Toxicon, 2026)

Tannic acid protects against lapatinib-induced hepatotoxicity by inhibiting cathepsin activity and repairing lysosomal membrane permeabilization - Yuan Mu; Zengyue Pan; He Zhao; Xiangliang Huang; Nini Zhang; Zhifei Xu; Bo Yang; Qiaojun He; Xiaochun Yang; Peihua Luo; Hao Yan (Toxicology and Applied Pharmacology, 2026)

Manganese-amended constructed wetlands coupled with microbial fuel cells significantly enhance methane mitigation: synergistic mechanisms of electrochemical source suppression and manganese-mediated terminal oxidation - Lingyun Mu; Wenjuan Zhai; Xinshan Song; Yunkun Qian; Zhongshuo Xu; Wei Huang (Journal of Environmental Chemical Engineering, 2026)

Sustainable high internal phase emulsions based on millet bran nanocellulose and EGCG: Centrifugal fabrication, antioxidant reinforcement, and 3D printability - Mo Chen; Yu-hao Wu; Xu Guo; Jin-yue Sun; Nan Chen; Mu-xuan Wang; Qi-dong Ren; Mohamed A. Farag; Nilufar Z. Mamadalieva; Min Wang; Meng-qi Zhang; Chao Liu (Food Chemistry, 2026)

Enhanced lactulose production by computer-aided design of cellobiose 2-epimerase - Zhaolin Huang; Wei Xu; Wenli Zhang; Aliaksandr Kastsianevich; Leanida Sapunova; Dawei Ni; Wanmeng Mu (Food Bioscience, 2026)

In vitro screening and probiotic evaluation of lactic acid bacteria exhibiting potential to enhance intestinal barrier function and antioxidant properties - Shishen Liu; Lu Feng; Haijun Mu; Shenhuizi Chen; Xue Han; Qian Xu (Food Bioscience, 2026)

Oral immunization of Nile tilapia with Chlorella-bioencapsulated multi-epitope fusion antigen effectively protects against Streptococcus agalactiae infection - Xiaodong Deng; Zichun Xiao; Dan Mu; Dianlong Xu; Juncai Li; Yuxuan Yang; Hanjie Gu; Yonghua Hu; Xiaowen Fei (Fish & Shellfish Immunology, 2026)

Rare earth Ce3+/Ce4+ redox effect coupled S-scheme heterojunction synergistically boost electron transfer for efficient photocatalytic environmental remediation - Dongyu Xu; Jiangyu Wang; Pengshuai Yin; Jing Zhang; Situ Mu; Li He; Chun Liu (Environmental Research, 2026)

Unraveling health disparities across cause-specific outcomes associated with emerging air pollutants: Evidence on black carbon and ultrafine particles in Buffalo, New York - Xuewen Pei; Muwu Xu; Harshita Sharma; Marina Oktapodas Feiler; Riana R. Pryor; Lina Mu; Meng Wang (Environmental Research, 2026)

Competitive inhibition underlies Cr(III) toxicity to soil arylsulfatase: Kinetic transitions during aging and molecular validation of detoxification mechanisms - Qiuting Yan; Wanli Xu; Rongyu Mu; Mallavarapu Megharaj; Haixia Tian; Wenxiang He (Environmental Pollution, 2026)

Mangrove-root-inspired bionic three-dimensional trapezoidal prismatic interfacial evaporator for efficient salt-resistant and oily seawater purification - Xinxin Zeng; Xiaotong Mu; Chenzhao Bai; Haoyu Yue; Yucai Xie; Zhiwei Xu; Hongsheng Zhang; Hongpeng Zhang; Chengqing Yuan (Desalination, 2026)

Enhanced levansucrase expression in Bacillus subtilis via regulatory element optimization for high-yield lactosucrose production from sucrose and lactose - Hangbin He; Yang Yang; Qiang Wei; Xiaoyong Liu; Wei Xu; Wenli Zhang; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

A Systematic Survey and Geoconservation Strategy for Geoheritage Resources in the Guang’an Region, Southwest China - Sibao Zhu; Hong-Xu Mu; Zizheng Wang; Qingwei Song; Minghui Li; Qing Zhou; Jun Liu; Bangguo Zhou; Canhai Jin (Geoheritage, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Silicon addition mitigates nitrogen-induced reduction in community stability by increasing species asynchrony, species richness and dominant species stability - Wenhong Zhou; Danghui Xu; Zhengwei Ren; Yuqi Wu; Baiyin Huang; Wenbo Mu; Zhaoliang Song; Wei Mu; Yawen Gui (Acta Oecologica, 2026)

Genome-wide investigation of methyl-CpG-binding domain genes in Brassica napus L. and functional characterization of BnaC09.MBD7 and BnaA10.MBD7 in modulating osmotic stress tolerance - Ling Jiang; Gang Lin; Mufei Shi; Jingying Wu; Lixuan Sun; Xiumei Xu; Zhihua Zhang; Shiyao Wen; Meifeng Chen; Xiewang Gao; Mu Xiao (Physiology and Molecular Biology of Plants, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Rapid growth and super air stability of 2D ultrathin superconducting Mo2C crystals - Zhandong Mu; Wen Teng; Wei Guo; Qiang Wang; Chen Chen; Zhibo Liu; Yongfeng Wang; Ning Kang; Chuan Xu; Wencai Ren (Science Bulletin, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Variable silicate weathering and enhanced reverse weathering during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; Denglin Han; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chun-Yao Liu; Ke Xu; Can Chen; Mu Liu; Daizhao Chen (Geochimica et Cosmochimica Acta, 2026)

Tuning oxygen vacancy density via facet engineering of TiO2 for selective photocatalytic hydrogenation of 5-hydroxymethylfurfural - Yunlei Zhang; Chaoyue Xu; Xiaotong Mu; Hongke Li; Jian Cao; Maobin Wei; Peng Wang; Yao Chen (Fuel, 2026)

Removal of acetaminophen and total nitrogen from secondary effluent via a UV/PAA-biofilter process: Efficiency, biofilm characteristics, and reaction mechanism - Kun’ao Du; Congwei Luo; Mingshan Yin; Ran Zou; Ning Guo; Yao Xu; Shiqi Bai; Xue Jiang; Xiaoxiang Cheng; Liping Qiu; Daoji Wu; Ruimin Mu (Environmental Research, 2026)

Achieving 9.11 GHz broadband microwave absorption in CeO₂/Sn@C composites via Sn doping and structural modulation - Yecheng Qiu; Hao Ma; Jinhua Du; Wei Li; Xiaolong Wang; Yizhe Tian; Xu Mu; Defang Duan; Yingnan Wang (Chemical Engineering Journal, 2026)

Self-assembly-confined upconversion photogelation enables centimeter-deep curing for rapid deep-organ hemostasis with sustained pain modulation - Qian Chen; Hongyu Wen; Peng Zhang; Xuhui Xu; Hanying Wang; Guizhu Feng; Qiqi Pei; Li Tian; Yuanyuan Cao; Hongwei Qin; Fusheng Luo; Zhaowei Teng; et al. (Chemical Engineering Journal, 2026)

Practical applications of graphene-based flexible adhesive respiratory monitoring sensor for daily and clinical monitoring - Deqiang Zhang; Shengtian Mu; Wenhua Wu; Qinqin Xu; Zhen Zheng; Yang Li; Xinkai Deng (Chemical Engineering Journal, 2026)

Photothermal-amplified single-atom platinum nanozymes on black phosphorus for deep antibacterial therapy - Bairui Zeng; Dongyang Zheng; Anni Wu; Yanjing Zhang; Peng Ding; Zhixiang Mu; Junhao Xiang; Shuangshuang Xu; Xiaoliang Qi; Jianliang Shen; Zhennan Deng (Chemical Engineering Journal, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

OS-SBDA: a dual-track Schrödinger Bridge adversarial framework for unpaired optical-to-SAR image translation - Wenjun Zhu; Jiangfu Xu; Xiangli Nie; Zihao Gao; Yang Yi; Yimin Mu; Mengyi Zhang (International Journal of Remote Sensing, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

Association of microplastic pollution with coral resilience in the presence of sea surface temperature anomalies - Xu Dong; Xiangang Hu; Kaishuo Lu; Kai Hu; Li Mu (Journal of Hazardous Materials, 2026)

AI-2–mediated quorum sensing marks the ecological transition from collective cooperation to individual survival during Daqu storage - Boyang Xu; Hao Zhou; Shanshan Xu; Ruijuan Wang; Qinxiang Xu; Xuefeng Wu; Dongdong Mu; Xingjiang Li (International Journal of Food Microbiology, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Interaction between segmented lining and surrounding rock considering sliding layer for compressed air energy storage caverns - Liqi Mu; Yanshuo Hou; Lijuan Cheng; Caichu Xia; Chen Xu; Duofeng Cen; Ruixiang Chen; Angel Garcia-Fontanet Molina; Alfonso Rodriguez-Dono (Tunnelling and Underground Space Technology, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Engineering a 2-methylimidazole framework nanozyme for efficient oxidation of lactose to lactobionic acid under mild conditions - Donghui Xie; Yanna Jiao; Shaoyi Yu; Jia Tu; Yunhui Cheng; Xiaohong He; Daichen Mu; Keyu Xing; Zhou Xu (Journal of Environmental Chemical Engineering, 2026)

High-precision identification of industrial inorganic wastes via dual-layer machine learning: Coupling major geochemical matrices with trace-level fingerprints - Zongyu Mu; Qingqi Die; Siqi Xu; Zhimin Zheng; Jinzhong Yang; Ruixiao Huang; Qifei Huang; Yufei Yang (Journal of Environmental Chemical Engineering, 2026)

Stage-specific environmental responses and divergent distributional shifts of Antarctic krill under climate change in the Cosmonaut Sea - Xiuxia Mu; Xianyong Zhao; Chongliang Zhang; Yunxia Zhao; Qingchang Xu; Jichang Zhang; Yiping Ying; Lu Liu; Jianfeng He; Peiru Luo; Xinliang Wang (Journal of Environmental Management, 2026)

Comparison of nitrogen oxides (NO, NO2) analyzers from controlled conditions in a 100 m3 outdoor simulation chamber to field observations - Xuanming Huang; Xiaowei He; Jinzhao Tong; Baobin Han; Shichuan Ni; Zhiwei He; Xuelian Zhong; Xinmiao Xu; Min Cai; Yang Wang; Chenyang Xue; Wenya Niu; et al. (Journal of Environmental Sciences, 2026)

Short-term and lagged effects of ambient air pollution on emergency visits for cardiovascular diseases modified by meteorological factors - Hong Mu; Yufeng Shi; Jiexin Liu; Zhicheng Hu; Xia Wang; Yue Wang; Bin Xu; Rongshan Wu; Jian Xu (International Journal of Hygiene and Environmental Health, 2026)

Organic association of U, Mo, V, and Ni in Neogene coals from the Puyang Mine, Yunnan, southwestern China - Zhenyu Xu; Xingxing Guo; Xiaomei Wang; Haoran Yang; Ke Sheng; Yuanhe Mu; Xingwang Ren; Baoqing Li (International Journal of Coal Geology, 2026)

Integration of network toxicology, transcriptomics and metabolomics reveals the novel neurotoxic mechanisms of diazepam and its metabolites - Xu Xiaodong; Li Jiaxin; Li Zimeng; Yang Zhen; Qiao Lu; Xu Jinhua; Qi Bohao; Hu Xin; Ren Yuanyuan; Li Jiongtang; Mu Yingchun (Food and Chemical Toxicology, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

The effect of activation on algal char catalyst's physiochemical properties and catalytic performance of algae pyrolysis - Shannan Xu; Zhiqiang Liu; Jiangyi Zhou; Yayuan Xiao; Zhe Zhang; Mao Mu; Shuang Wang (Biomass and Bioenergy, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Isolation and Characterization of Vibrio crassostreae S2 Associated with Mass Mortality in Manila Clams Ruditapes philippinarum - Zhixin Mu; Weibo Shi; Ya Li; Zhili Shi; Kai Liao; Jilin Xu; Weiwei Zhang (Journal of Ocean University of China, 2026)

Microbial Perspective: Regulatory Mechanisms of Interactions Between Microplastics and Dissolved Organic Matter on Greenhouse Gas Emissions in Aquatic Ecosystems - Mengxin Xu; Meiqi Huang; Shuang Liu; Jinze He; Feng Zhao; Bo Shao; Guangli Mu; Hongyang Cui; Panpan Cui; Yingxin Zhao; Yiwen Liu; Xiaoyu Cui; et al. (Global Change Biology, 2026)
Microplastic (MP) pollution may influence aquatic greenhouse gas (GHG) emissions by altering dissolved organic matter (DOM)–microbe coupling, yet reported effects remain inconsistent across ecosystems and exposure regimes. Here, we synthesized evidence from 16 studies to quantify the net effects of MPs on CO 2 , CH 4 , and N 2 O fluxes under ambient DOM conditions. Our meta‐analysis indicates that MP exposure significantly increases CO 2 emissions and decreases N 2 O fluxes, whereas CH 4 responses show a non‐significant positive trend with high variability. Exposure duration and polymer identity emerge as key moderators, indicating that MP effects are context‐dependent rather than uniform. Short‐term exposure tends to suppress carbon mineralization, whereas long‐term exposure is more often associated with GHG production, consistent with a time‐dependent trajectory potentially shaped by polymer aging. Mechanistically, this pattern may reflect initial DOM adsorption and humification that reduce substrate availability, followed by the release of bioavailable MP‐derived compounds that may stimulate microbial respiration, methanogenesis, and denitrification. Overall, MPs reshape aquatic carbon and nitrogen cycling within the overarching framework of DOM, which may ultimately influence GHG emissions under certain conditions. These findings provide a quantitative basis for reconciling conflicting observations and improving predictions of the climate relevance of MP pollution in aquatic ecosystems.

Compressive sensing based seismic data acquisition a case study in northeast China - Jian-guo Chen; Guo-xu Shu; Sheng-qiang Mu; Yi-yuan Wang; Shou-dong Huo (Applied Geophysics, 2026)

Effects of Second-Order Wave Forces on the Extreme Response Estimation of the TLP Offshore Wind Turbine Under Multi-Directional Wind-Wave Loads - Jiahao Mu; Wei Shi; Linyang Cao; Jinghong Shang; Xu Han; Yang Yang; Liang Liu; Guangyuan Cheng (Journal of Marine Science and Engineering, 2026)
As offshore wind energy advances into deeper waters, the dynamic response and safety assessment of tension leg platform (TLP) wind turbines under complex marine conditions have become focal research points. This study investigates a 15 MW TLP wind turbine, acquiring data on motion responses, mooring tensions, and tower-base loads through time-domain analysis, with extreme value estimation conducted using the mean up-crossing rate method. The results indicate that under normal operating conditions, second-order wave forces significantly influence extreme response estimation. At an exceedance probability of 0.01, the second-order sum-frequency force increases the extreme tower base shear by 4.28% and the bending moment by 10.11% compared to the first-order-only case, while the difference-frequency force has a minor effect. Different wind-wave incidence angles cause distinct variations in turbine motion, with head-on incidence exciting the largest wave-frequency responses and lateral incidence producing relatively weaker excitation effects. Furthermore, the coupling effect between incident direction and second-order wave forces further amplifies extreme response risks. Therefore, it is essential to fully assess the prevailing wind-wave directions in the target sea area and consider the effects of second-order wave forces, especially the sum-frequency component, to ensure the long-term safe operation of TLP wind turbines under complex sea conditions.

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Atomically precise Pd4 cluster on monolayer MoS2 for efficient overall water splitting - Yuxin Xu; Jing Ma; Tao Ma; Jiehang Wei; Mengjia Fu; Wenjuan Wang; Shouqin Mu; Xin Wang; Yingtao Liu (Fuel, 2026)

Integrated kinetic and multi-omics analysis reveal the internal responses of density-dependent growth inhibition in Lactobacillus bulgaricus - Wenjing Xu; Xiaocen Chen; Yan Xu; Tao Wu; Xiaoqing Mu (Food Bioscience, 2026)

Bisphenol analogs affected hepatic development and disrupted lipid homeostasis in zebrafish larvae - Yao Zheng; Ying Huang; Jiajia Li; Liyan Teng; Yanyang Xu; Lilai Yuan; Wenbo Yang; Jing Qiu; Yongzhong Qian; Tingting Chai; Xiyan Mu (Environmental Pollution, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Layered double hydroxides vs. metal-organic frameworks: Which enables more sustainable phosphate fertilizer production from sludge? - Xiaole Wang; Qian Zhao; Xiaoxiang Cheng; Jingtao Xu; Shujuan Meng; Yifan Zhao; Kechao Han; Ruimin Mu; Lei Liu (Journal of Environmental Chemical Engineering, 2026)

Seawater pH fluctuations during the Ordovician to Silurian transition: Insights from δ11B records in carbonates - Xiangrong Yang; Shaojie Li; Detian Yan; Yue Cai; Denglin Han; Ke Xu; Yanqing Li; Can Chen; Peng Sun; Mu Liu; Chunyao Liu; Daizhao Chen (Global and Planetary Change, 2026)

Enhancing solar-driven biomass gasification through multi-catalyst strategies: Catalytic mechanisms, product regulation, and energy conversion - Xiankun Huang; Yong Wang; Zhang Bai; Xiaoli Zhu; Lianlian Xu; Xinyu Mu; Binzhong Xi (Fuel, 2026)

Comprehensive screening strategy for potentially hazardous plant secondary metabolites in honey using natural deep eutectic solvent extraction combined with LC-MS/MS - Yuzhe Yuan; Guodong Mu; Haitao Xu; Xiaofeng Xue; Sha Yan (Food Chemistry, 2026)

Evaluation of iron supplementation effects of whey protein peptide-ferrous chelate: enhancing bioavailability and antioxidant capacity, promoting gut microbiota balance - Yanan Xu; Yumei Wu; Haiyue Zhang; Zezhen Ma; Guangqing Mu; Fang Qian (Food Chemistry, 2026)

Combinatorial PPTase screening and systematic metabolic engineering for high-level indigoidine production in Corynebacterium glutamicum - Jiali Zhang; Zeyu Li; Rui Lu; Junsong Xiao; Yingying Zhu; Wei Xu; Wanmeng Mu (Food Bioscience, 2026)

Storage-driven metabolic shifts in daqu microbiota regulate flavor formation during baijiu fermentation - Boyang Xu; Lijun Yan; Hao Zhou; Shanshan Xu; Ruijuan Wang; Qinxiang Xu; Xuefeng Wu; Dongdong Mu; Xingjiang Li (Food Bioscience, 2026)

Synergistic cross-linked network and electron-rich 0D/1D heterostructure enable high-performance PEO-based lithium metal batteries - Tengxiao Mu; Chen Wen; Yongsheng Yao; Min Li; Gang Wang; Liwen Yang; Zengsheng Ma; Guobao Xu (Chemical Engineering Journal, 2026)

Corrigendum to “Mussel-inspired polysaccharide-based sponges for hemostasis and bacteria infected wound healing” [Carbohydrate Polymers 295 (2022) 119868] - Wen Sun; Changjun Mu; Xu Zhang; Hengchong Shi; Qiuyan Yan; Shifang Luan (Carbohydrate Polymers, 2026)

Experimental study and numerical analysis on the disinfection of exhaled bioaerosols by Trombe wall in a mechanically ventilated environment - Yu Qian; Jie Ji; Hao Xie; Jiyao Li; Suyue Xu; Hengmin Jia; Yan Mu (Building and Environment, 2026)

Study on the mechanism of mixed biochar enhancing methane production in anaerobic digestion of corn straw - Huilin Zhang; Siyu Zhang; Pujie Wei; Xinyue Zhao; Hong Chang; Zeyan Mu; Xu Zhang; Wei Liu; Xudan Liu; Xiaohong Su; Xin Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Real-time detection and characterization of trunks and upright branches of pear trees for automatic dormant pruning - Hao Sun; Gengchen Wu; Hu Xu; Jiaqi Li; Zhidi Zhou; Shutian Tao; Wei Guo; Kaijie Qi; Hao Yin; Shaoling Zhang; Seishi Ninomiya; Yue Mu (Precision Agriculture, 2026)

Bioaccumulation and Elimination, and Risk Assessment of Diazepam in Carp (Cyprinus Carpio) - Zhen Yang; Xiaodong Xu; Ying Li; Xin Hu; Jinhua Xu; Lu Qiao; Huiwu Sun; Yingchun Mu (Bulletin of Environmental Contamination and Toxicology, 2026)

Adaptations in ancient oasis woodlands of the hyper-arid Tarim Basin, Northwestern China: charcoal and coprolite analyses - Kangkang Li; Konglan Shao; Ying Yang; Gill Plunkett; Robert Spengler; Bing Xu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Guijin Mu; et al. (Archaeological and Anthropological Sciences, 2026)

A Genetically Defined Thalamic Circuit Encodes Social Touch - Shuyan Geng; Chuanyao Sun; Xing Liu; Zixu Zhang; Shengru Hu; Hao Jiang; Xiaoxia Xue; Tianxiang Xu; Wei Xie; Mingdao Mu (Neuroscience Bulletin, 2026)

Research progress in microbial synthesis of D-allulose using metabolically engineered microbes - Junchi Zhu; Like Fan; Jiajun Chen; Wei Xu; Azis Boing Sitanggang; Fina Amreta Laksmi; Junmei Ding; Wanmeng Mu (Trends in Food Science & Technology, 2026)

Treatment of shale gas fracturing flowback fluid using a novel multistage flocculation reactor: Energy-matching mechanism and field validation - Xing Liang; Can Cui; Lulu Xu; Yumin Mu; Gang Jin; Chang Liu; Liang Li; Haijun Zhang; Xiaobing Li (Process Safety and Environmental Protection, 2026)

Tamarisk miRNA target genes TcSPL5 and TcNAC1 mediate the post-transcriptional responses of salt stress - Yang Zheng; Junwen Wang; Meng Xu; Mu Cao; Shaoyan Jiang; Jianwen Wang; Li-an Xu (Plant Science, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Mining allergens in Cryptotympana atrata nymphs: integrating proteomics and homology-based bioinformatics - Yuan He; Shu-tao Sun; Jian-bo Xiao; Qi-dong Ren; Ying-ying Chen; Meng-qi Zhang; Mu-xuan Wang; Xu Guo; Jin-yue Sun; Chao Liu (Food Chemistry, 2026)

Deoxynivalenol induces testicular inflammation via mtDNA leakage-mediated activation of the cGAS-STING pathway in mice - Haihua Huo; Gaolong Zhong; Peixuan Li; Feiyang Chen; Yunpeng Deng; Lu Guan; Jiabin Chen; Yan Wang; Xu Wang; Qingmei Chen; Jikai Wen; Yiqun Deng; et al. (Food Bioscience, 2026)

Identification of a novel and thermostable laccase from Bacillus velezensis GLY4 and its application in the biotransformation of aflatoxins - Xin Zhang; Binbin Ouyang; Wei Xu; Hongbin Sun; Wanmeng Mu (Food Bioscience, 2026)

An overview of the physical, chemical and biological strategies for the removal of emerging mycotoxins: Recent advances and future perspectives - Jiayi Yao; Binbin Ouyang; Wei Xu; Yanli Xie; Wanmeng Mu (Food Control, 2026)

Semi-analytical solution for bidirectional strain-softening behavior of surrounding rock mass in compressed air energy storage caverns - Liqi Mu; Chen Xu; Caichu Xia; Shishu Zhang; Angel Garcia-Fontanet Molina; Alfonso Rodriguez-Dono (Computers and Geotechnics, 2026)

Decoupling effects of driving factors on sediment load in the middle reaches of the Yellow River - Chaohui Ma; Xiaoxue Guo; Ruirui Xu; Peng Gao; Jiahui Zhou; Yuxuan Zhang; Xingmin Mu (CATENA, 2026)

COL8A1-positive cancer-associated fibroblasts are drivers of 5-fluorouracil resistance in colorectal cancer - Muzi Ding; Yue Li; Zixuan Liu; Shangshang Hu; Jinwei Lou; Yuhan Chen; Jian Qin; Mu Xu; Huiling Sun; Tao Xu; Shukui Wang; Yuqin Pan (Apoptosis, 2026)

A Miniature A-Mode Ultrasound System for Noninvasive Bone Surface Point Cloud Acquisition - Tianya Xu; Chuanba Liu; Jiayang Mu; Pengbo Wang; WenJuan Ma; Xiqi Jian; Jiumin Yang; Yanqiu Zhang (Annals of Biomedical Engineering, 2026)

Liver-specific SLC13A3 modulation alleviates MASLD by regulating NAD+ metabolism - Jiangxia Du; Minhui Shen; Yuan Mu; Shuoran Peng; Zhifei Xu; Xiaochun Yang; Bo Yang; Peihua Luo; Hao Yan; Qiaojun He (Molecular and Cellular Biochemistry, 2026)

Inversion modeling of rice chlorophyll content based on optimized UAV hyperspectral remote sensing image data - Xiaotong Mu; Zhongyu Jin; Zhonghui Guo; Juchi Bai; Fenghua Yu; Tongyu Xu (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Superhydrophilic and underwater superoleophobic three-dimensional chitosan@Cu-MOF aerogel for effective oil/water separation - Le Yin; Mu Hu; Chu Xu; Yuan Wang; Shaojun Yuan (Journal of Environmental Chemical Engineering, 2026)

Biomineralization and genome-based insights of Fe(III) reduction of the NaCl-tolerant Tessaracoccus oleiagri from an integral oilfield - Xinghao Liu; Jianbin Li; Fangyi Mu; Ding Dong; Dehao Lu; Jie Yang; Ting Xu; Shuyuan Deng; Fan Zhang; Yuehui She; Hao Dong (Journal of Environmental Chemical Engineering, 2026)

Recycling acid-leaching clay wastewater to synthesize bimetallic metal-organic frameworks for efficient removal of Pb2+ and UO22+ - Mingcai Ma; Bin Mu; Jiang Xu; Yushen Lu; Aiqin Wang (Journal of Environmental Sciences, 2026)

Enhanced performances of iron-rich sludge ash for chemical looping gasification of pretreated rice straw by the modification of transition metal oxides - Ying Dai; Jinpeng Jiang; Xiran Xu; Meng Sun; Xiaoyuan Wang; Lin Mu; Jianbiao Chen; Yuezhao Zhu; Jinzhu Tan (Fuel, 2026)

Dual-readout digital colorimetric assay for zearalenone in corn based on alkaline phosphatase mediated growth of Prussian blue nanoparticles - Shanghong Ji; Tingtiao Pan; Weizhen Xu; Song Tang; Guodong Mu; Zeyu Hu; Yu Zhou (Food Chemistry, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Decoding the pharmacokinetics of intravenous lentinan: A multiscale journey from the blood to hepatic Kupffer cells' lysosomes - Xu Mu; Jinglin Wang; Shuai Wan; Jingyi Wang; Lei Huang; Nire Wu; Yuxue Zhan; Yuxuan Liu; Yu Zhang; Ziming Zheng; Kan Ding; Kaiping Wang (Carbohydrate Polymers, 2026)

A Medial Paralemniscal Pth2ergic Circuit Contributing to Aversive and Anxiety-Like Behaviors - Zixu Zhang; Shuyan Geng; Chuanyao Sun; Shengru Hu; Tianxiang Xu; Wei Xie; Mingdao Mu (Neuroscience Bulletin, 2026)

Insight into the Evolution of Mitochondrial Genetic Basis of Amphibious Adaptation in the Goby (Teleostei: Gobiidae) - Chengyao Yang; Chaoyang Luo; Qiuping Wang; Xionghui Xu; Juan Zhang; Chengfa Zhao; Yuan Mu; Datian Lang; Wenxian Hu (Journal of Molecular Evolution, 2026)

Beyond astaxanthin: The bioactive ingredients of Haematococcus pluvialis and their applications in food - Shu-tao Sun; Yan-jie Jiang; Jesus Simal-Gandara; Xu Guo; Shengxiang Yang; Ying-ying Chen; Meng-qi Zhang; Qi-dong Ren; Mu-xuan Wang; Jin-yue Sun; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2026)

Variability of near-inertial internal wave energy in the Kuroshio extension from CPIES array observations - Y.R. Mu; Y.S. Xu; J.H. Park (Progress in Oceanography, 2026)

Efficient removal of tetracycline and norfloxacin by KOH-activated carbon derived from Forsythia Fructus residue - Jigang Wang; Yuxin Liu; Dandan Qian; Lihuan Xu; Yingying Guo; Chunyan Jiang; Yajuan Mu (Journal of Water Process Engineering, 2026)

Seasonal dynamics of microbial diversity and ecological functions in the river estuary area of Loushan River - Xin Hu; Chengci Liu; Jinhua Xu; Zhiyang Zhao; Hongyu Jin; Xiaodong Xu; Lu Qiao; Zhen Yang; Jincheng Li; Mutai Bao; Lei Huang; Yingchun Mu (Journal of Hydrology, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Spatial characterization and health risk evaluation of residual phenol five years after a river pollution incident - Tingting Liu; Fengjing Song; Yiming Sun; Zhen Ding; Hao Zheng; Shixuan Hao; Hong Xu; Yan Liu; Chao Wang; Xiaomin Xie; Mu Zhu; Peixuan Shen; et al. (Journal of Hazardous Materials, 2026)

Identification and in-silico screening of ACE-inhibitory peptides from casein hydrolysate via fermentation with different probiotics - Ruiqi Ren; Lu Liu; Xiaodong Li; Xiuxiu Zhang; Min Xu; Zhixing Zhang; Xuezhen Wang; Bingbing Mu; Xianlu Zhang; Aruna Zhou (International Dairy Journal, 2026)

Corrigendum to “An overview of cyclodextrin on the detection and removal of mycotoxin: Recent advances and future prospects” [165 (2024) 110660] - Yan Shi; Wei Xu; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Control, 2026)

AE-TD3 with adaptive expert guidance: towards responsive deep reinforcement learning for building HVAC control systems - Zeqing Wu; Yunfei Mu; Xiaolong Jin; Yanze Xu; Hongjie Jia; Jun Zhao (Energy and Buildings, 2026)

A multifunctional ion-conductive hydrogel with supramolecular interactions for wearable sensing: Human motion monitoring and Morse code communication - Ying Chen; Shenghua Lv; Leipeng Liu; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She (Chemical Engineering Journal, 2026)

Asymmetric nanochannels for high sensitive detection of AFB1 - Xinrui Xu; Lingxiao Liu; Qianyu Yang; Bin Du; Bing Liu; Xihui Mu; Zhaoyang Tong (Chemical Engineering Journal, 2026)

Efficient generation and utilization of high-valent cobalt-oxo in nanoconfined catalytic membranes for enhanced antibiotic degradation - Wei Zhang; Kaiming Fan; Mu Li; Weihua Xu; Yanling Liu; Shengji Xia (Chemical Engineering Journal, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

Discovery of novel nuciferine-based URAT1 inhibitors for hyperuricemia: synthesis, biological evaluation, and computational insights - Yan-fei Liu; Ze-sheng Hao; Xu Guo; Shu-tao Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Jin-yue Sun; Chao Liu (Medicinal Chemistry Research, 2026)

Design of Sn-doped MoS2 piezocatalyst for high-efficiency antibiotic degradation: mechanism and performance - Mingyang Xu; Xiang Wang; Jingyu Yu; Zhenlin Mu; Shengjun Yang; Chenxi Guo; Guoxuan Li; Yinglong Wang; Fanqing Meng (ENGINEERING Environment, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

An automated and high-throughput approach to profile betaine lipids in microalgae - Yanrong Li; Tong Mu; Zhujun Zhu; Yuanyuan Fu; Jilin Xu; Xiaojun Yan (Algal Research, 2026)

A hybrid model driven by remotely-sensed data for simulating the impact of high spatiotemporal variations in fertilization and atmospheric N2O on N2O emissions in paddy fields - Wei Jiang; Xiang Gao; Housheng Wang; Xuerong Lang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan zhang; Xiaosan Jiang; Jinyang Wang; Yanfeng Ding; et al. (Agricultural and Forest Meteorology, 2026)

Ground validation of dust multi-properties analyzer onboard Tianwen-2 - Xu Tan; Cunhui Li; Jiajie Wang; Zhongcheng Mu; Zecheng Cui; Meng Chen; Xin Ren; Xiaodong Liu; Yan Su; Wei Wang; Renhao Tian; Jiawei Li (Advances in Space Research, 2026)

Optimized Design and Experimental Evaluation of a Vibratory Screening Unit for Mactra veneriformis Harvesting on Intertidal Mudflats Based on the Discrete Element Method - Bin Xu; Shuyuan Liang; Yuzhong Lou; Jixuan Zhao; Hangqi Li; Yizhi Chang; Hao Wu; Guangcong Chen; Gang Mu (Fishes, 2025)
To enhance shell–mud separation and overall harvesting efficiency for Mactra veneriformis under intertidal mudflat conditions, a vibratory harvesting device driven by a crank–rocker mechanism that produces approximately rectilinear simple-harmonic motion was developed. Dynamic analysis of clam motion on the screen deck identified vibration amplitude, vibration frequency, excitation direction angle, and screen deck inclination angle as key determinants of screening performance. Single-factor tests, a Plackett–Burman design, a steepest-ascent experiment, and response surface methodology (RSM) optimization were conducted. Their influences on forward travel speed ranked as follows: screen deck inclination angle > excitation direction angle > vibration amplitude > vibration frequency. The optimized settings were vibration amplitude of 8.5 mm, excitation direction angle of 45°, screen deck inclination angle of 11°, and vibration frequency of 10 Hz. Intertidal mudflat trials yielded a harvesting efficiency of 342 kg/h and a clam breakage rate of 4.6%, meeting the design targets. After harvesting, the shear strength of the mudflat decreased, with disturbance mainly confined to the surface layer, thereby meeting the low-disturbance requirement and enabling ecologically friendly harvesting. These results provide a basis for the design and optimization of M. veneriformis harvesting machinery.

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Incorporating spatiotemporal structure to improve the understanding of Antarctic krill (Euphausia superba) distribution - Xiuxia Mu; Xinliang Wang; Chongliang Zhang; Xianyong Zhao; Jichang Zhang; Yunxia Zhao; Yiping Ying; Gangzhou Fan; Lu Liu; Jiancheng Zhu; Qingchang Xu (Fisheries Research, 2025)

Physics-informed neural network for hydraulic prediction in open-channel water transfer projects with sparse monitoring data - Zhongbin Li; Tong Mu; Xin Li; Pengcheng Li; Jiangang Feng; Hui Xu; Chunsheng Liu; Shangtuo Qian (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

A mechanistic, distributed model for coupled simulation of soil water-plant, groundwater and surface flow system in arid/semi-arid agricultural watersheds (SurfMOD)—Model description and evaluation - Danning Mu; Xu Xu; Xue Xiao; Tiago B. Ramos; Chen Sun; Xinyi Li; Yihao Xun; Guanhua Huang (Journal of Hydrology, 2025)

From mung bean to Minglv-flavor baijiu: Unraveling the signature aroma profile and aging dynamic - Ruijuan Wang; Lijun Yan; Feng Ding; Shanshan Xu; Weiqi Hu; Ling Zhang; Boyang Xu; Hao Zhou; Dongdong Mu; Xingjiang Li (Food Chemistry, 2025)

Quaternized poly(arylene piperidine) anion exchange membranes with enhanced alkaline stability and desalination performance - Tong Mu; Zhibo Zhang; Leicheng Guo; Geting Xu; Junbin Liao; Jianquan Weng; Jiangnan Shen; Congjie Gao (Desalination, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Demand-driven grafting engineering of IMC/PAM ionic conductive hydrogel: Multifunctional platforms for wearable sensors and TENGs - Ying Chen; Shenghua Lv; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

taVNS alleviates preeclampsia-induced vascular endothelial dysfunction via α7nAChR- IP3R1/GRP75/VDAC1 signal pathway - Jing Zhao; Yuman Lei; Chengcheng Mu; Yuwei Wu; Rourou Fang; Dongdong Wu; Shouzhu Xu; Haifa Qiao (Inflammation Research, 2025)

Evaluation of mechanical properties and geological features of highly sandy dolomite: consequences for engineering safety - Meiqian Wang; Wei Xu; Hongzhong Xu; Hongyuan Mu; Jian Mi; Yonghong Wu; Yangxing Wang; Baofa Cai (Bulletin of Engineering Geology and the Environment, 2025)
The Central Yunnan Water Diversion Project (CYWD Project) is a crucial water source initiative within Yunnan’s revitalization strategy. However, significant engineering challenges arise, such as tunnel mud and water inrush due to the presence of highly sandy dolomite. Therefore, understanding the mechanical properties of this dolomite is essential for ensuring safe construction in the tunnel engineering of the CYWD Project. This paper examines the highly sandy dolomite found in the Sinian strata of Zbdn and Zbd, located along the Yuxi section of the tunnel line, using both micro and macro testing methods. Microscopic analyses, including slice identification, CT scanning, and scanning electron microscopy, were conducted to determine the primary geological characteristics and classification standards of the sandy dolomite. Additionally, macro tests, such as in-situ needle penetration tests (NPT), uniaxial compressive strength tests (UCS), and shear tests, were performed. Using the least squares method and regression analysis, relationships between the needle penetration index (NPI), UCS, and shear strength were established. This study established reliable relationships between the needle penetration index, uniaxial compressive strength, and shear strength parameters of highly sandy dolomite encountered in the CYWD Project. The geological features were also characterized using macro- and micro-scale testing, providing a theoretical basis for the project’s design and safety. This conversion relationship offers a theoretical basis for the design, construction, and safety evaluation of the CYWD Project. The parameters developed are sufficiently reliable for evaluating engineering in areas with highly sandy dolomite. Graphical abstract

A hybrid model based on machine learning and improved Jayaweera-Mikkelsen model to simulate NH3 volatilization in paddy field water - Xuerong Lang; Xiang Gao; Housheng Wang; Wei Jiang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan Zhang; Jinyang Wang; Yanfeng Ding; Yue Mu; et al. (Agricultural and Forest Meteorology, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

ERO1A-positive tumor epithelial cells in colorectal cancer progression: a multi-omics perspective - Shangshang Hu; Jinwei Lou; Yuhan Chen; Muzi Ding; Jian Qin; Junjie Nie; Yue Li; Zixuan Liu; Mu Xu; Huiling Sun; Qianni Xiao; Yuqin Pan; et al. (Apoptosis, 2025)

Towards sustainable separation of fuel additives - containing azeotrope by energy-saving extractive distillation process - Xiang Wang; Zhifan Chen; Jingyu Yu; Zhenlin Mu; Ying Xu; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Guoxuan Li (Process Safety and Environmental Protection, 2025)

Far-UVC photolysis of NaClO for iopamidol degradation: Role of reactive substances, degradation mechanisms and ecotoxicity - Yao Xu; Hongxiang Wang; Congwei Luo; Mingshan Yin; Xiaoxiang Cheng; Kunyu Chen; Yan Jin; Ruimin Mu; Jingtao Xu; Daoji Wu; Xuedong Zhai (Journal of Water Process Engineering, 2025)

Evaluation of harmful impact of low concentration cylindrospermopsin through zebrafish behavioral endpoints under multiple life stages - Minghui Fu; Yining Zhang; Linjie Luo; Minglu Wu; Liyan Teng; Jiandong Mu; Guohua Xiao; Yanyang Xu; Jing Qiu; Tingting Chai; Yongzhong Qian; Guijie Hao; et al. (Journal of Hazardous Materials, 2025)

Reverse-tracing unravels microbial succession and flavor stratification driven by vertical physicochemical gradients in Zaopei fermentation - Boyang Xu; Shanshan Xu; Hao Zhou; Qinxiang Xu; Hui Zhang; Dongdong Mu; Xuefeng Wu; Eryong Zhao; Xingjiang Li (Food Chemistry, 2025)

Microbial and enzymatic strategies for aflatoxin control: Integrating intelligent detection and computational design - Binbin Ouyang; Wei Xu; Dawei Ni; Wenli Zhang; Junmei Ding; Wanmeng Mu (Food Chemistry, 2025)

Metagenomics and binning analysis unveiled the diversity and transfer patterns of antibiotic resistance genes in traditional pickled vegetables - Hui Wang; Xindi Mu; Tingting Su; Xiyuan Yang; Lei Xu; Di Yao; Liangyu Li (Food Bioscience, 2025)

Comprehensive assessment of full-cycle high-solid anaerobic digestion of straw for methane production update: Focus on performance improvement and circular economy - Yingjin Song; Yinjie Zhong; Yanshan Wang; Lan Mu; Yuxing Luo; Sheng Xu; Huiling Niu; Zhi Wang; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Construction of MXene/gelatin foam hydrogel with multi-stage porous for efficient solar-driven interfacial evaporation and ion removal - Jialong She; Shenghua Lv; Tingxiang He; Ying Chen; Yanlu Mu; Jinru Liu; Jing Xu; Xiangyi Liu; Leipeng Liu (Chemical Engineering Journal, 2025)

Why not use tertiary amines to prepare anion-exchange membranes for desalination with electrodialysis? - Shuaijun Yu; Yixiang Yu; Yan Zhang; Yangbo Qiu; Tong Mu; Ming Li; Zhipeng Xu; Qiang Wei; Jiangnan Shen (Chemical Engineering Journal, 2025)

The effect and interaction mechanism of different iron (hydr-) oxides on the degradation of benzo (a) pyrene by Paracoccus sp. HPD-2 - Xinhong Gan; Yudong Chen; Yang Xu; Tingting Mu (Archives of Microbiology, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Insufficient telomeric DNA damage response promotes chromosomal instability in aged oocytes - Tianqi Cao; Simiao Liu; Fang Wang; Min Gao; Wenlian Wu; Yanling Qiu; Ming Mu; Tengteng Xu; Jinkun Wen; Yuxi Chen; Haiying Liu; Xiqian Zhang; et al. (Science Bulletin, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

The oldest known Curvicubitidae (Hemiptera) from the Permian (Wuchiapingian) of Zhangshu City, Jiangxi Province, southern China - Qian-Qi Zhang; Lin Mu; Lei Zhang; Xu-Heng Du; Hai-Chun Zhang (Palaeoworld, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

KOH-activated carbon derived from Siraitia grosvenorii shells for efficient removal of methylene blue and tetracycline - Yuxin Liu; Jigang Wang; Lihuan Xu; Dandan Qian; Yajuan Mu (Journal of Environmental Chemical Engineering, 2025)

Metabolites from Lactobacillus delbrueckii subsp. bulgaricus DLPU F-36 and L-Arginine promote immune tolerance to whey protein in rats by modulating Th1/Th2 and Th17/Treg balance - Zhao Zhang; Yanchen Liu; Yunpeng Xu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Microencapsulation of Acer truncatum seed oil using chickpea protein isolate–low/high-methoxy citrus pectin complex coacervates: Preparation, stability analysis, and application in milk - Mo Chen; Bo Zhang; Min Wang; Jin-yue Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Qi-dong Ren; Shu-tao Sun; Mohamed A. Farag; Xu Guo; Chao Liu (Food Hydrocolloids, 2025)

Distribution patterns and assembly mechanisms of microbial communities in the riverine waters of southeastern Tibet - Yanhong Wang; Zhao Hao; Enyong Chen; Jianping Xu; Shuaishuai Huang; Qiong La; Pengxi Cao; Xiu Zhang; Junwei Wang; Nanmujia Pingcuo; Quzhen Baima; Jiawei Li; et al. (Environmental Research, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

Efficient peroxymonosulfate activation by γ-Al2O3 nanosheets supported FeS2 for neonicotinoids removal: Role of surface hydroxyl-enhanced activation and sulfur-facilitated iron redox cycling - Zhiqiang Xu; Meng Zhang; Hongxin Mu; Simin Li; Yuanqing Bu; Houhu Zhang (Chemical Engineering Journal, 2025)

Phase-interfacial engineering of 2H@1 T-WS2-x cocatalyst to accelerate H2 production on SnS2 - Jianchun Wang; Nan Mu; Ruixin Xu; Xin Hong; Yanyu Liu; Wei Zhou (Chemical Engineering Journal, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Study the photocatalytic mechanism of the novel Ag/p-Ag2O/n-BiVO4 plasmonic photocatalyst for the simultaneous removal of BPA and chromium(VI)” [Chem. Eng. J. 361 (2019) 1352–1362] - Wei Zhao; Jin Zhang; Fengxia Zhu; Feihu Mu; Lili Zhang; Benlin Dai; Jiming Xu; Anfeng Zhu; Cheng Sun; Dennis Y.C. Leung (Chemical Engineering Journal, 2025)

A novel pre-oxidation of ultrafiltration membrane fouling mitigation via ascorbic acid-activated hydrogen peroxide - Yao Xu; Congwei Luo; Mingshan Yin; Xiaoxiang Cheng; Xinyu Zhang; Yan Jin; Ruimin Mu; Jingtao Xu; Kun'ao Du; Xue Jiang; Shiqi Bai; Daoji Wu; et al. (Chemical Engineering Journal, 2025)

Water and sediment yield in the source region of the Yellow River, northeastern Tibetan Plateau: Historical pattern, future evolution, and attribution analysis - Ruirui Xu; Dexun Qiu; Peng Gao; Xingmin Mu (CATENA, 2025)

Production and characterization of copolymers consisting of 3-hydroxybutyrate and adjustable lactate by engineered Halomonas bluephagenesis from glucose - Jiangnan Chen; Fang Yang; Xinyu Chen; Yiling Chen; Zhenghao Xu; Shi Mu; Guo-Qiang Chen (Bioresource Technology, 2025)

Design and testing of the clam vibration harvester's V-shaped double-spiral harvesting roller brush based on DEM-MBD - Li Hangqi; Mu Gang; Li Xiuchen; Wu Hao; Xu Bin; Liu Fawei; Sun Zhenyin; Zhang Qian; Zhang Hanbing; Xin Mingjin; Zhang Guochen (Aquacultural Engineering, 2025)

What does the dairy farming bring to the desertified soil? A case study - Zixi Han; Jianfei Zeng; Xu Zhao; Yanyan Dong; Yongsong Mu; Sha Wei; Yong Hou; Ziyu Han (Agricultural Systems, 2025)

Two novel 5,5-spiroketal sesquiterpenoid isomers from the roots of Angelica biserrata (R. H. Shan &Yuan) C. Q. Yuan & R. H. Shan - Fuyong Ni; Rongrong Li; Zixian Xie; Ying Li; Ningning Xu; Xuanyu Mu; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Xue Xie; Wei Xiao (Natural Product Research, 2025)

Mining robust in situ phosphorus-accumulating organisms via single-cell RACS-Culture for rational ecosystem engineering - Xiaoyan Jing; Yanhai Gong; Yishang Ren; Liyan Wang; Runzhi Mu; Pengcheng Sun; Zhidian Diao; Yu Meng; Liming Huang; Xixian Wang; Jia Zhang; Jiaxuan Luan; et al. (Water Research, 2025)

Recent advances on health effects and biological production of functional monosaccharide d-mannose - Yehong Cao; Yihan Chen; Wei Xu; Yingying Zhu; Wenli Zhang; Dawei Ni; Wanmeng Mu (Trends in Food Science & Technology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Wind-tide modulated net ecosystem metabolism in a Changjiang River Estuary aquaculture zone during mid-autumn - Di Wu; Kui Wang; Guoquan Wang; Qinglin Mu; Wei Fan; Dawei Xu (Marine Environmental Research, 2025)

Unraveling long-term water consumption changes and agro-ecological responses to agricultural practices in arid irrigation districts of the upper Yellow River basin (2000–2021) - Xinyi Li; Pu Wang; Jiaxin Mu; Danning Mu; Chen Sun; Zhengzhong Li; Dongyang Ren; Zailin Huo; Xu Xu (Journal of Hydrology, 2025)

A runoff prediction approach based on machine learning, ensemble forecasting and error correction: A case study of source area of Yellow River - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Baiyinbaoligao; Jiahua Wei; Jie Gao; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2025)

A generative ozone concentration imputation and forecasting method based on a novel conditional diffusion model - Liangliang Mu; Suhuan Bi; Kai Yan; Xiangqian Ding; Yan Xu (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Identification of a novel DON dehydrogenase and computational insights into the decisive role of cofactor affinity in DON detoxification - Binbin Ouyang; Zhaolin Huang; Chengfei Wang; Yurong Sun; Junmei Ding; Wei Xu; Wanmeng Mu (Food Bioscience, 2025)

Unraveling the main chemical mechanism of PM2.5 pollution caused by open burning of sugarcane straw during winter in southern China: The Pivotal Role of NOx and NH3 Oxidation-Neutralization - Xu Wei; Guiyun Liang; Jingying Mao; Junchao Yang; Yijun Mu; Chuan Nong; Dabiao Zhang; Jiahui Lu; Xishou Huang; Ying Wu; Zhaoyu Mo (Environmental Pollution, 2025)

MXene-CuS pyramid array photothermal structures inspired by Roman broccoli for solar-driven water evaporation and power generation - Xiaotong Mu; Xinxin Zeng; Zhiwei Xu; Hongpeng Zhang; Chenzhao Bai; Yucai Xie; Yu Liu (Chemical Engineering Journal, 2025)

Surface electronic state regulation of Cs3Cu2I5 via In2O3 heterojunction for room-temperature H2S detection - Weihua Yang; Shasha Gao; Danhong Gao; Xianjie Xu; Zhefu Mu; Xinjian He; Sheng Huang (Chemical Engineering Journal, 2025)

Functional expression of proton pumps in Rhodobacter sphaeroides enhanced energy supply and photo-fermentative hydrogen production - Xuefang Mu; Yuntong Xu; Yu Ma; Zixuan Gao; Jiali Feng; Minmin Wang; Wen Cao; Liejin Guo (Bioresource Technology, 2025)

Stage-specific responses of whitespotted conger (Conger myriaster) body condition to environmental variability and climate change - Xiuxia Mu; Chongliang Zhang; Yupeng Ji; Binduo Xu; Ying Xue; Yiping Ren (Hydrobiologia, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Contaminant transport in a municipal solid waste landfill: On-site assessment and numerical modelling of vertical barrier wall effectiveness - Lin Mu; Qiao Wang; Fusheng Zha; Jun Wang; Rumin Xu; Miao Piao (Waste Management, 2025)

Nitrogen uptake and nitrification in the Changjiang estuary - Xing Hou; Chongcong Liu; Guodong Song; Jinglong Mu; Wen Liang; Haoming Xu; Nian Wu; Wenqi Xu; Su Mei Liu (Marine Environmental Research, 2025)

The driving effect of marine industries on marine pollution: Empirical evidence from coastal China - Cong Yu; Zifei Liu; Xianghui Kong; Runsheng Pei; Wanchanok Umprasoet; Yongtong Mu; Jun Xu (Journal of Cleaner Production, 2025)

Modes of occurrence of rare earth elements and yttrium in bituminous coals with different ranks from the Hedong Coalfield, northern China - Zhenyu Xu; Xiaomei Wang; Fan Deng; Xingxing Guo; Yuxuan Han; Ke Sheng; Yuanhe Mu; Qin Yang (International Journal of Coal Geology, 2025)

Poly(aryl piperidine) anion exchange membrane with self-assembled siloxane crosslinked networks for efficient ion separation in alkaline waste treatment via electrodialysis - Yazhen Jiang; Tong Mu; Ning Ding; Yangke Pan; Geting Xu; Junbin Liao; Edison Huixiang Ang; Jiangnan Shen (Desalination, 2025)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Formyl-phloroglucinol meroterpenoids with Nrf2 inhibitory activity from Eucalyptus globulus leaves - Wei Liu; Yaodong Xia; Lejie Zhang; Xin Chen; Zhuo Zhang; Yu Mu; Jialin Xu; Xueshi Huang; Liya Li (Phytochemistry, 2025)

Triple microenvironment synergy engineering by grain boundaries of hydrophilic Cu electrode for boosting low-concentration nitrate electroreduction - Xin Wang; Qinian Wang; Mu Yuan; Xu Cheng; Bo Zhang; Ke Zhang; Lili Wang; Chao Wu; Xing Zhang (Chemical Engineering Journal, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Mechanistic insights into substituent-induced hydrolytic debromination and electron flow of bromophenols under nitrate-reducing conditions - Yunhao Xu; Jing Wang; Qiang Chi; Peng Zheng; Hanjuan Lv; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

A robust CMCNa-PAM salt-inhibiting double-network hydrogel for efficient solar interfacial evaporation - Junzhe Huang; Jianhua Zhou; Yang Long; Xiaojiang Mu; Zhixiang Zhang; Yanqing Zhu; Gang Xu; Jing Liu; Jun-Liang Chen; Lei Miao (Journal of Environmental Chemical Engineering, 2025)

Effect of interlayer anions NO3- and SO42- on NH3-SCR performance of LDHs precursor catalyst - Fan Xu; Guilin Mu; Lianzheng Zhang; Yixin Ma; Shanshan Liu (Journal of Environmental Chemical Engineering, 2025)

Unveiling the Characteristics of Microbiota in Different Mucosal Layers of Leopard Coral Grouper (Plectropomus leopardus) - Jiahui Wang; Shengtao Gao; Zhenyuan Xu; Zhihui Yang; Qianqian Mu; Zijian Li; Pingping Liu; Jingjie Hu; Zhenmin Bao (Marine Biotechnology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The effect of Hydrogen-rich water on retinal degeneration in the outer nuclear layer of simulated weightlessness rats - Yuxue Mu; Weihang Li; Dongyu Wei; Xinyi Zhang; Lilingxuan Yao; Xiaofeng Xu; Xiaocheng Wang; Zuoming Zhang; Tao Chen (Life Sciences in Space Research, 2025)

Synergism of cold extrusion and ball milling for improving rheological properties of whey protein isolate - Yue Liu; Heyang Xu; Munkh-Amgalan Gantumur; Nan Yang; Akhunzada Bilawal; Zhanmei Jiang; Zhishen Mu (Food Hydrocolloids, 2025)

Effects of neonicotinoid pesticide exposure in the first trimester on gestational diabetes mellitus based on interpretable machine learning - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Yonghong Sheng; Yang Xu; Dongping Huang; Shun Liu; Xiaoyun Zeng; Virasakdi Chongsuvivatwong; Xiaoqiang Qiu (Environmental Research, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Smart temperature sensors based on flexible CB/TPU/ PVDF membranes for eliminating pressure interference - Shuo Li; Jiaxin Sun; Feng Tong; Guo Chen; Zhefu Mu; Xiaoqiang Zhang; Sheng Huang; Zheng Chen; Lei Xu; Changyun Li; Peng Wang; Xiuquan Gu (Chemical Engineering Journal, 2025)

Strategies to reduce CH4 and N2O emissions whilst maintaining crop yield in rice–wheat system under climate change using SPACSYS model - Shuhui Wang; Nan Sun; Zhijian Mu; Fa Wang; Xiaojun Shi; Chuang Liu; Shuxiang Zhang; Joost Wellens; Bernard Longdoz; Jeroen Meersmans; Gilles Colinet; Minggang Xu; et al. (Agricultural Systems, 2025)

Comparison of elemental composition and 87Sr/86Sr-143Nd/144Nd between fossil and modern fish teeth and the significance of the enrichment of REE in deep-sea sediments - Zhijie Xu; Xiaoyu Zhang; Kongyang Zhu; Mu Huang; Miao Yu; Zheng Li; Zhongrong Qiu; Yanfang Lu (Frontiers in Marine Science, 2025)
Fossil fish teeth are important carriers of rare earth elements (REEs) in deep-sea sediments. Meanwhile, 87 Sr/ 86 Sr- 143 Nd/ 144 Nd in these fossils have been widely used in paleoceanography. However, when and how REEs enter the fish teeth remains ambiguous, which hinders elucidating the enrichment mechanism of REEs in deep-sea sediments, and the effectiveness of 87 Sr/ 86 Sr- 143 Nd/ 144 Nd in paleoceanography is doubted. This study examined the contents of REEs, major and trace elements, and 87 Sr/ 86 Sr- 143 Nd/ 144 Nd in modern fish teeth and in fossil fish teeth from deep-sea sediments. The results indicated that elemental geochemical properties and a redox environment are the main factors controlling their enrichment process in fish teeth. At least three categories of trace elements are classified during two different stages (physiological process of living fish and post-deposition of fossils): (1) elements of Type I mainly belong to IA, IIA, IIIA, IVA, and transition group with active chemical properties, entering into the fish teeth during life; (2) Type II represents elements from the IA, VA, transition elements, and Actinides groups, and are enriched uninterruptedly from the living fish teeth to the post-deposition fossils with variable valences under different redox conditions; (3) Type III are elements accumulated only after deposition under oxidizing or suboxidizing and are members of Lanthanides and rare dispersed elements groups with a large atomic radius and strong chemical activity. The distinctly different enrichment processes of Sr and Nd, 87 Sr/ 86 Sr, and 143 Nd/ 144 Nd in fossil fish teeth may represent different material sources and should be cautiously employed in paleoceanography. The continuous rehabilitation of 87 Sr/ 86 Sr in fossil fish teeth after deposition would change the original 87 Sr/ 86 Sr of seawater recorded near fish teeth but the content of Sr remains unchanged. As for 143 Nd/ 144 Nd, when Nd enters the fossils after deposition, the exchange of 143Nd/144Nd between particles and pore liquid gradually ceases due to the saturation of the isomorphism lattice. 143 Nd/ 144 Nd of fossil fish teeth may provide more information about deep seawater at the seawater-sediment interface. This study elucidates the enrichment mechanism of REEs in deep-sea sediments and the cautious utilization of 87 Sr/ 86 Sr and 143 Nd/ 144 Nd of fossils is a prerequisite.

Development and evaluation of high-throughput HD-Marker arrays in pacific white shrimp (Litopenaeus vannamei) - Mingyang Liu; Zhihui Yang; Xin Huang; Qifan Zeng; Qianqian Mu; Zhenyuan Xu; Zijian Li; Pingping Liu; Shi Wang; Jingjie Hu; Zhenmin Bao (Aquaculture, 2025)

Polydopamine-modified coal fly ash composite electrodes for improved electroadsorption of uranium - Jianfeng Zhang; Yifei Jiang; Mu You; Jing Zhao; Shuwen Xue; Hongxia Fang; Yijun Wei; Zhimei Sun; Tao Zeng; Ziqi Wan; Mai Xu; Yunhu Hu (Journal of Water Process Engineering, 2025)

Do emerging alternatives pose similar soil ecological risks as traditional plasticizers? A multi-faceted analysis using earthworms as a case study - Huijuan Lv; Baoyan Mu; Haixia Xu; Xianxu Li; Xiangfeng Yao; Qian Wang; Huiyan Yang; Jia Ding; Jun Wang (Journal of Hazardous Materials, 2025)

Recycled wheat straw biochar enhances nutrient-poor soil: Enzymatic kinetics of carbon, nitrogen, and phosphorus cycling - Qiuting Yan; Haixia Tian; Yi Huang; Xiangli Mu; Guangmu Tang; Haigang Ma; Mallavarapu Megharaj; Wanli Xu; Wenxiang He (Journal of Environmental Management, 2025)

Distinguishing the botanical origins of rare honey through untargeted metabolomics and machine learning interpreting flavonoid profiles - Sha Yan; Yuzhe Yuan; Fei Pan; Guodong Mu; Haitao Xu; Xiaofeng Xue (Food Chemistry, 2025)

Probiotic potential of lactic acid bacteria with antioxidant properties in modulating health: Mechanisms, applications, and future directions - Yuan Gao; Qimeng Liang; Junqi Sun; Xiaomeng Wu; Yinglong Song; Yunpeng Xu; Hui Nie; Jun Huang; Guangqing Mu (Food Bioscience, 2025)

Photo-stimulating dual-network microminiature hydrogels reinforced with silver sulfide nanoparticles for regulated cancer photothermal therapy - Rongqiu Mu; Guanghui Gu; Youyin Xu; Yongming Xi; Gang Wei (Chemical Engineering Journal, 2025)

The use of isomerases and epimerases for the production of the functional sugars mannose, allulose and tagatose from Fructose - Junya Yang; Yingying Zhu; Xu Wei; Dawei Ni; Wenli Zhang; Wanmeng Mu (World Journal of Microbiology and Biotechnology, 2025)

Comparative lipidome revealed an increase of unsaturated lipids in Bifidobacterium animalis subsp. lactis 420 by linoleic acid supplementation - Qing Liao; Shuyan Wu; Ziyi Tang; Xi Yang; Ming Huang; Xing Weng; Xia Yu; Xiaoyuan Wang; Mu Zhang; Meijuan Xu; Xiaoqing Hu (Systems Microbiology and Biomanufacturing, 2025)

Self-gelated flexible lignin-based ionohydrogels for efficient self-powered strain sensors - Jiahui Mu; Cuihuan Li; Deqiang Li; Xianliang Song; Sheng Chen; Feng Xu (Chemical Engineering Journal, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

An optimized non-landslide sampling method for Landslide susceptibility evaluation using machine learning models - Shuai Xu; Yingxu Song; Pin Lu; Guizhen Mu; Ke Yang; Shangxiao Wang (Natural Hazards, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Regulatory Roles and Therapeutic Potential of miR-122-5p in Hypoxic-Ischemic Brain Injury: Comprehensive Review - Abdulaziz S. Bamahel; Xun Sun; Wei Wu; Chenxi Mu; Jia Liu; Sheng Bi; Hui Xu (Cell Biochemistry and Biophysics, 2025)

Integrated Navigation Algorithm for Autonomous Underwater Vehicle Based on Linear Kalman Filter, Thrust Model, and Propeller Tachometer - Haosu Zhang; Yueying Cai; Jin Yue; Wei Mu; Shiyin Zhou; Defei Jin; Lingji Xu (Journal of Marine Science and Engineering, 2025)
For the purpose of reducing the cost, size, and weight of the integrated navigation system of an AUV (autonomous underwater vehicle), and improving the stealth of this system, an integrated navigation algorithm based on a propeller tachometer is proposed. The algorithm consists of five steps: ① establishing the resistance model of AUV, ② establishing the thrust model, ③ utilizing the measured speeds obtained from the AUV’s voyage trials for calibration, ④ discrimination and replacement of outliers from the tachometer measurements, and ⑤ establishing a linear Kalman filter (LKF) with water currents as state variables. This paper provides the modeling procedure, formula derivations, model parameters, and algorithm process, etc. Through research and analysis, the proposed algorithm’s accuracy has been improved. The specific values of the localization error are detailed in the main text. Therefore, the proposed algorithm has high accuracy, a strong anti-interference capability, and good robustness. Moreover, it exhibits certain adaptability to complex environments and value for practical engineering.

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

An overview of the chirality of diet-related fatty acids, glycerolipids, and glycerophospholipids - Shu-tao Sun; Yan-jie Jiang; Xu Guo; Meng-qi Zhang; Qi-dong Ren; Jesus Simal-Gandara; Mu-xuan Wang; Xiao-jia Xue; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Ecological distribution of ammonia oxidizers in Yellow River sediments and their influencing factors - Xue Lou; Mengxin Xu; Mingyang Wang; Yining Jiang; Minggang Zheng; Hongyu Mu; Shuai Liu; Shaoping Kuang; Hui Chen; Zhiyao Wang (Environmental Research, 2025)

Platinum nanoparticles confined in Zn-S-1 for efficient propane dehydrogenation - Shuwang Li; Lei Wang; Mu Niu; Junbiao Wu; Yide Han; Yan Xu; Jianhua Zhu; Zhuopeng Wang (Chemical Engineering Journal, 2025)

Why are the Qinling Mountains Significant to China? - Xing Chen; Yanjun Shen; Qingyi Mu; Panpan Xu; Fenghao Duan; Jianbing Peng (Journal of Earth Science, 2025)

Analytical expressions of specific yield for shallow groundwater estimation and modeling - Xue Xiao; Yuheng Yang; Danning Mu; Chaojie Li; Guanhua Huang; Xu Xu (Environmental Monitoring and Assessment, 2025)

Accessory minerals fingerprint post-collisional anatectic metamorphism in continental collision zones - Yong-Jie Yu; Ren-Xu Chen; Qiong-Xia Xia; Zhi-Hui Mu; Zhuang-Zhuang Yin; Guo-Chao Sun (Lithos, 2025)

Bi2O2CO3/Bi2O2+S1- S-scheme n-n heterojunction with boosted photocatalytic degradation for bisphenol A - Weina Mu; Lijuan Wang; Jingsan Xu; Chun Chang (Journal of Environmental Management, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

Overcoming radiation-induced PD-L1 upregulation by novel gadolinium-palladium nanoplatforms for enhanced tumor radio-immunotherapy - Kai Guo; Hui Liu; Mengmeng Zhang; Nengyi Ni; Mengyao Mu; Ke Ren; Jiahui Chen; Qing Fan; Xueli Xu; Xiao Sun; Ximing Wang (Chemical Engineering Journal, 2025)

Characterization of deoxynivalenol dehydrogenase from Pelagibacterium sp. SCN 63–126 and its application - Wei Xu; Jiayi Yao; Jingbo Ma; Chen Lu; Chenfei Wang; Yurong Sun; Cuie Guang; Wanmeng Mu (Archives of Microbiology, 2025)

The Characteristics of Sex Differentiation Based on Morphological Traits During the Early Development Stage of the Swimming Crab Portunus trituberculatus and Sex Prediction Model Comparison - Yanqing Peng; Junkai Lu; Ronghua Li; Chendong Xu; Shangbiao Zheng; Zhiming Ren; Chuan He; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2024)
To investigate the morphological traits of different sexes during the early development stage of the swimming crab Portunus trituberculatus, the genetic sex of 405 crablets from stages C I–V was determined using sex-linked molecular markers. The external appearance of each crab was observed, and the morphological traits, including carapace length (CL), full carapace width (FCW), abdomen width (AW), and abdomen length (AL), were measured to compare the differences between the sexes and to develop non-intrusive methods for sex identification. The genetic sex identification demonstrated that the female-to-male sex ratio at each stage did not deviate from 1:1. The gonopores of the females were first observed at stage C I using a scanning electron microscope; however, the shape difference in the abdominal flap between the sexes from stages C I to stage C V were not observed under a dissecting microscope. Correlation analysis showed that AW3 and AW4 were significantly correlated with sex at stage C V. Three methods were used to predict the sex of the crablets according to the morphological measurements; among them, the multinomial logistic regression (MLR) model performed better than the threshold method or the stepwise discriminant analysis, and the accuracy at stage C V increased to 90% when detailed abdominal parameters were included. These results indicate that it is feasible to predict sex during the early development stages of P. trituberculatus through morphometric and geometric parameters, which would be helpful for the creation of monosex populations of this species.

A comprehensive review on the properties, production, and applications of functional glucobioses - Shuqi Zhang; Dawei Ni; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Preparation of agriculture film from cow manure for silage maize planting: Experimental study and life cycle assessment - Zixi Han; Xu Zhao; Bingxin Tong; Yongsong Mu; Xiangjun Yang; Yong Hou; Zhiping Zhu (Waste Management, 2024)

Improvement of NDVI mixture model for fractional vegetation cover estimation with consideration of shaded vegetation and soil components - Xihan Mu; Yang Yang; Hui Xu; Yuhan Guo; Yongkang Lai; Tim R. McVicar; Donghui Xie; Guangjian Yan (Remote Sensing of Environment, 2024)

Acetylcholinesterase inhibitory phloroglucinols from tropic Rhodomyrtus tomentosa - Ling-Yun Chen; E-E Luo; Yu Pan; Cheng-Qin Liang; Mu-Yuan Yu; Xu-Jie Qin (Phytochemistry, 2024)

Phytocannabinoid-like meroterpenoids from twigs and leaves of Rhododendron spinuliferum - E-E Luo; Wu-Fen Yang; Zhao-Jie Wang; Ling-Yun Chen; Mu-Yuan Yu; Xiao-Dong Luo; Xu-Jie Qin (Phytochemistry, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

Exploring formation of turanose in honey via stable isotope labelling and high-resolution mass spectrometry analysis - Yuzhe Yuan; Sha Yan; Liming Wu; Haitao Xu; Guodong Mu; Xiaofeng Xue (Food Chemistry, 2024)

The relationships between flavor substances and microbial communities during the fermentation of Chinese traditional red sour soup - Xin Zhang; Zhenyu Wang; Xianbing Xu; Xin Mu; Baifeng Fu; Jinxiu Xu; Shuhong Ye; Ming Du (Food Bioscience, 2024)

Opportunities and challenges in developing promising mycotoxin-degrading enzymes with high thermostability and strong pH activity/stability - Binbin Ouyang; Wenli Zhang; Cuie Guang; Wei Xu; Wanmeng Mu (Food Bioscience, 2024)

Directly mining and identifying a cellobiose 2-epimerase with isomerization activity by phylogenetic analysis - Zhaolin Huang; Binbin Ouyang; Jiajun Chen; Guocong Luo; Dawei Ni; Wei Xu; Wanmeng Mu (Food Bioscience, 2024)

Efficient phosphate recovery and treatment of high-phosphorus wastewater using sodium alginate-immobilized microspheres based on aluminum-rich water treatment plant sludge - Guorui Li; Wei Zhu; Jun Zhong; Jipeng Sun; Yichao Wang; Biao Mu; Xin Wang; Yucheng Xu (Environmental Pollution, 2024)

Ecotoxicological risk of co-exposure to fosthiazate and microplastics on earthworms (Eisenia fetida): Integrating biochemical and transcriptomic analyses - Chonglin Xu; Xiangfeng Yao; Weizheng Kong; Baoyan Mu; Guilan Duan; Jun Wang; Yuxin Xu; Xianxu Li (Environmental Pollution, 2024)

Iron-Induced vacancy and electronic regulation of nickle phosphides for ampere-level alkaline water/seawater splitting - Linbo Jiang; Lintao Jiang; Xu Luo; Ruidong Li; Qingqu Zhou; Lin Wang; Lei Chen; Shichun Mu (Chemical Engineering Journal, 2024)

A green and sustainable technology for the development of artificial protein fibers from sorghum distillers grains for industrialization - Yuanyi Shao; Bingnan Mu; Lan Xu; Yiqi Yang (Chemical Engineering Journal, 2024)

Insights into oral lentinan immunomodulation: Dectin-1-mediated lymphatic transport from Peyer's patch M cells to mononuclear phagocytes - Kaiping Wang; Yuxuan Liu; Zeming Zhang; Ziming Zheng; Wenqi Tang; Wangtianzi Teng; Xu Mu; Jinglin Wang; Yu Zhang (Carbohydrate Polymers, 2024)

Cellulose-based colorimetric/ratiometric fluorescence sensor for visual detecting amines and anti-counterfeiting - Cuihuan Li; Yuan He; Jiankang Zhang; Jiahui Mu; Junya Wang; Mengyao Cao; Haq Nawaz; Sheng Chen; Feng Xu (Carbohydrate Polymers, 2024)

Luteinizing Hormone Receptor Mutation (LHRN316S) Causes Abnormal Follicular Development Revealed by Follicle Single-Cell Analysis and CRISPR/Cas9 - Chen Zhang; Yongqiang Nie; Bufang Xu; Chunlan Mu; Geng G. Tian; Xiaoyong Li; Weiwei Cheng; Aijun Zhang; Dali Li; Ji Wu (Interdisciplinary Sciences: Computational Life Sciences, 2024)
Abnormal interaction between granulosa cells and oocytes causes disordered development of ovarian follicles. However, the interactions between oocytes and cumulus granulosa cells (CGs), oocytes and mural granulosa cells (MGs), and CGs and MGs remain to be fully explored. Using single-cell RNA-sequencing (scRNA-seq), we determined the transcriptional profiles of oocytes, CGs and MGs in antral follicles. Analysis of scRNA-seq data revealed that CGs may regulate follicular development through the BMP15-KITL-KIT-PI3K-ARF6 pathway with elevated expression of luteinizing hormone receptor (LHR). Because internalization of the LHR is regulated by Arf6 , we constructed LHR N316S mice by CRISPR/Cas9 to further explore mechanisms of follicular development and novel treatment strategies for female infertility. Ovaries of LHR N316S mice exhibited reduced numbers of corpora lutea and ovulation. The LHR N316S mice had a reduced rate of oocyte maturation in vitro and decreased serum progesterone levels. Mating LHR N316S female mice with ICR wild type male mice revealed that the infertility rate of LHR N316S mice was 21.4% (3/14). Litter sizes from LHR N316S mice were smaller than those from control wild type female mice. The oocytes from LHR N316S mice had an increased rate of maturation in vitro after progesterone administration in vitro. Furthermore, progesterone treated LHR N316S mice produced offspring numbers per litter equivalent to WT mice. These findings provide key insights into cellular interactions in ovarian follicles and provide important clues for infertility treatment. Graphical Abstract

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Identification of a thermostable L-asparaginase from Pyrococcus yayanosii CH1 and its application in the reduction of acrylamide - Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Extremophiles, 2024)

Model test and numerical simulation of open caisson foundation under long-term lateral loading - Baogang Mu; Xu Ling; Weifeng Zheng; Guoxiong Mei; Pengpeng Ni (Ocean Engineering, 2024)

Accumulation and depuration of 4,5-dihydro-KmTx2 from Karlodinium veneficum in the bivalves, Mercenaria mercenaria and Sinonovacula constricta - Yanrong Li; Rong Chen; Zhujun Zhu; Tong Mu; Zhaoshou Ran; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2024)

An overview of cyclodextrin on the detection and removal of mycotoxin: Recent advances and future prospects - Yan Shi; Wei Xu; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Control, 2024)

Sub-chronically exposing zebrafish to environmental levels of methomyl induces dysbiosis and dysfunction of the gut microbiota - Mingxiao Li; Xi Chen; Chao Song; Limin Fan; Liping Qiu; Dandan Li; Huimin Xu; Shunlong Meng; Xiyan Mu; Bin Xia; Jun Ling (Environmental Research, 2024)

Multimodal spatiotemporal drug assessment platform based on a microelectrode neural network chip in Alzheimer’s disease - Fan Gao; Wei Xu; Yan Xiao; Wei Jiang; Mu Chen; Zekai Liu; Peng Zhang; Tianyi Yang; Zhiyu Qian; Keqiang Gao (Chemical Engineering Journal, 2024)

Seasonal simulation and source apportionment of SO42− with integration of major highlighted chemical pathways in WRF-Chem model in the NCP - Xiaoxi Zhao; Xiujuan Zhao; Dan Chen; Jing Xu; Yujing Mu; Bo Hu (Atmospheric Pollution Research, 2024)

Improving the activity of an inulosucrase by rational engineering for the efficient biosynthesis of low-molecular-weight inulin - Dawei Ni; Zhaolin Huang; Shuqi Zhang; Yang Yang; Xiaoyong Liu; Wei Xu; Wenli Zhang; Wanmeng Mu (Archives of Microbiology, 2024)

Recent developments of mycotoxin-degrading enzymes: identification, preparation and application - Yan Shi; Binbin Ouyang; Yulei Zhang; Wenli Zhang; Wei Xu; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Application of Fluorescent Composite Materials as a Sustained Release System in Treatment of Polycystic Ovary Syndrome - Lin Wang; Liangshan Mu; Yao Ye; Jun Xu; Xutong Zou (Journal of Fluorescence, 2024)

Nutrient requirements determined by grain yield and protein content to optimize N, P, and K fertilizer management in China - Xuemei Zhang; Zikang Guo; Junfeng Xu; Cui Huang; Haiyan Dang; Wenyan Mu; Lulu Zhang; Saibin Hou; Ning Huang; Chao Li; Yulan Ding; Ruiqing Sun; et al. (Science of The Total Environment, 2024)

A vapor phase side stream intensified extractive distillation process for separation of azeotropic mixture 2, 2, 2-trifluoroethanol and water - Dongmei Xu; Jinxing Mu; Hailin Sun; Sixuan Tao; Jun Gao; Zhishan Zhang; Lianzheng Zhang; Yixin Ma; Yinglong Wang (Process Safety and Environmental Protection, 2024)

The solar/chlorine system degradation of iopamidol: Roles of reactive species, degradation pathway, and toxicity - Ruidi Xu; Congwei Luo; Fan Yu; Daoji Wu; Jingtao Xu; Ruimin Mu; Xinyu Zhang; Qiao Ma; Feiyong Chen (Journal of Environmental Chemical Engineering, 2024)

High-temperature carbonization synthesis of coal fly ash/chitosan-carbon composite electrodes for enhanced uranium electroadsorption - Jianfeng Zhang; Mu You; Yijun Wei; Mai Xu; Yunhu Hu (Journal of Environmental Chemical Engineering, 2024)

Study on the microbial mechanisms of enhancing Agaricus bisporus growth through inoculation with Pseudomonas putida - Hongtu Li; Lanhua Liu; Boyang Xu; Xiaoming Yan; Qun Chen; Xiaolei Wu; Xunfeng Wu; Dongdong Mu; Xingjiang Li (Food Bioscience, 2024)

Mechanisms of single and mixed microbial fermentation to improve summer-autumn green tea - Xuandong Zheng; Shanshan Xu; Zhichao Yang; Lei Sun; Xuefeng Wu; Dongdong Mu; Xiangsong Chen; Xingjiang Li (Food Bioscience, 2024)

Evaluation of protective immune response of immersion inactivated vaccine against Singapore grouper iridovirus - Weihua Xu; Mengke Liu; Qiwei Qin; Jian Chen; Guanghui Mu; Dongzhuo Zhang; Xiaohong Huang; Youhua Huang (Fish & Shellfish Immunology, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Microalgae-derived hydrogels/membranes for phosphorus removal and recovery from aquaculture tailwater: Waste utilization and phosphorus recycling - Aihua Zhang; Shihao Fang; Mengni Ge; Jianfeng Zhang; Huan Xi; Yidan Xu; Zhuofan Gao; Zhuo Huang; Mu Liu (Bioresource Technology, 2024)

The mechanism of MMP14-positive tumor-associated fibroblast subsets in inhibiting PD-1 immunotherapy for esophageal cancer through exosomal tsRNA-10522 - Juzheng Wang; Chunlong Zheng; Jiayu Lu; Xinyao Xu; Guangyu Xiang; Jiahe Li; Jipeng Zhang; Xiaorong Mu; Qiang Lu (Functional & Integrative Genomics, 2024)

Modeling Rip Current Systems around Multiple Submerged Breakwaters - Jie Xu; Yuchuan Wang; Baoying Mu; Huan Du; Yanlei Li; Zaijin You; Sheng Yan; Lixin Lu (Journal of Marine Science and Engineering, 2024)
Multiple submerged breakwaters (MSBWs) are commonly used coastal protection structures due to their specific advantages over the emerged ones. Rip currents, as the inevitable natural hazard in the gaps of these constructions, are investigated numerically in the present study. A fully nonlinear mild-slope equation (NMSE) model possessing both fully nonlinear and fully dispersive properties is validated and adopted in the simulations. With four monochromatic wave conditions of different wave heights, periods and incidences representing low-energy, typical, storm and oblique waves tested, the flow patterns and the low-frequency oscillations of the rip currents are studied. For the convenience of risk assessment, the rip risk level is divided into three degrees according to the maximum rip flow speed. The effects of the configurations of the MSBWs on the rip current system as well as the rip risk level are examined, considering different breakwater widths, heights, forms, gap widths and gap numbers. Simulation results suggest that the cross-shore configurations of MSBWs influence the rip risk level by inducing different wave energy dissipations but the longshore configurations of MSBWs by changing flow field patterns.

Remediation on antimony-contaminated soil from mine area using zero-valent-iron doped biochar and their effect on the bioavailability of antimony - Jianghao Ji; Yizhen Mu; Siyi Ma; Siqin Xu; Xiaoying Mu (Chemosphere, 2024)

An accurate handheld device to measure log diameter and volume using machine vision technique - Min Xu; Shuai Chen; Shoushuai Xu; Baoyan Mu; Yue Ma; Jinghui Wu; Yue Zhao (Computers and Electronics in Agriculture, 2024)

Production of neomale and neofemale large yellow croaker (Larimichthys crocea) and establishment of all-female populations - Jialin Mu; Weihua Hu; Ruiyi Chen; Yang Yang; Haidong Li; Weiye Li; Xiaolong Yin; Dongdong Xu (Aquaculture, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Identification and application of a novel patulin degrading enzyme from Cyberlindnera fabianii - Chenyu Song; Wei Xu; Cuie Guang; Ting Xue; Wanmeng Mu (Food Research International, 2024)

Seven sour substances enhancing characteristics and stability of whey protein isolate emulsion and its heat-induced emulsion gel under the non-acid condition - Handa Cui; Zhishen Mu; Heyang Xu; Akhunzada Bilawal; Zhanmei Jiang; Juncai Hou (Food Research International, 2024)

Continuous flow hydrothermal synthesis of MoVNbTeOx in micro-coil tubular reactor for oxidative dehydrogenation of ethane - Yuxin Chen; Yuting Wu; Shuairen Qian; Zhengwen Li; Changyan Xu; Ruiqi Du; Yao Mu; Tianying Dai; Binhang Yan; Yi Cheng (Chemical Engineering Journal, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

A zero-dimensional perovskite with high-efficiency luminescence and transient response for advanced information encryption - Junheng Yuan; Tianchi Wang; Yu Zhang; Shuyi Yao; Lulu Han; Dedan Mu; Hao Song; Jiayi He; Feng Zhang; Xuhui Xu (Chemical Engineering Journal, 2024)

Bioaccumulation mediated by water solubility leads to differences in the acute toxicity of organophosphorus insecticides to zebrafish (Danio rerio) - Yujuan Liu; Yue Xu; Bingjie Yuan; Bingyu Zhu; Xiaobing Zhang; Jinyin Chen; Beixing Li; Wei Mu (Ecotoxicology, 2024)

Ultrasonic disaggregation of mixed-dimensional palygorskite clay for improving ABS resin properties - Jiang Xu; Lei Wu; Bin Mu; Yushen Lu; Qin Wang; Aiqin Wang (Applied Clay Science, 2024)

Complete genome sequence of a novel mitovirus isolated from the phytopathogenic fungus Alternaria alternata causing apple leaf blotch - Jichun Jia; Hanyang Liang; Lihong Cheng; Jinsheng Xia; Xu Chen; Baojun Zhang; Fan Mu (Archives of Virology, 2024)

Glycosylation of flavonoids by sucrose- and starch-utilizing glycoside hydrolases: A practical approach to enhance glycodiversification - Yuqing Tian; Wei Xu; Cuie Guang; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Middle Ordovician climatic and oceanic destabilization in a slope-setting of the Yangtze platform, South China, and its role as a regional brake on the Ordovician radiations - Chaogang Fang; Mu Liu; Chengcheng Zhang; Hailei Tang; Jianqing Li; Guangfu Xing; Fengjie Li; Naicen Xu; Tong Wu; Bo Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Transformer-based ozone multivariate prediction considering interpretable and priori knowledge: A case study of Beijing, China - Liangliang Mu; Suhuan Bi; Xiangqian Ding; Yan Xu (Journal of Environmental Management, 2024)

Bio-fuel production from hydroconversion of hexadecane over Pt/SAPO-11 catalysts - Chao Mu; Junhao Sun; Chen Xie; Jing Xu; Jinxuan Bao; Haozhe Zhang; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2024)

Exploring the relationship between GuaYi levels and microbial-metabolic dynamics in Daqu - Boyang Xu; Shanshan Xu; Hao Zhou; Ruijuan Wang; Chao Jiang; Dongdong Mu; Xuefeng Wu; Xiaolei Wu; Shaotong Jiang; Xingjiang Li (Food Bioscience, 2024)

Exploring Cr(VI)-induced blood-brain barrier injury and neurotoxicity in zebrafish and snakehead fish, and inhibiting toxic effects of astaxanthin - Mu-Yang Li; Yan-Chao Shi; Wan-Xin Xu; Lei Zhao; Ai-Zhong Zhang (Environmental Pollution, 2024)

Distinct electrochemical and metabolic responses of anode respiring bacteria to sulfamethoxazole in microbial fuel cells coupled with constructed wetlands - Ruimin Mu; Xiuhan Liu; Yunfei Li; Feiyong Chen; Yalan Shi; Jin Wang; Xue Shen; Linxu Xu; Yufeng Du; Zhigang Yang (Bioresource Technology, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Low-calorie bulk sweeteners: Recent advances in physical benefits, applications, and bioproduction - Jin Li; Quanyu Dai; Yingying Zhu; Wei Xu; Wenli Zhang; Yeming Chen; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

The giant African snail, Lissachatina fulica (Bowdich, 1822) in China: current status, threats and management - Wen Xiong; Qian Guo; Miao Fang; Meng Xu; Xidong Mu (Molluscan Research, 2024)

Recent advances in discovery, protein engineering, and heterologous production of ketose 3-epimerase for rare sugar biosynthesis - Jiajun Chen; Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Trends in Food Science & Technology, 2024)

B(a)P induces ovarian granulosa cell apoptosis via TRAF2-NFκB-Caspase1 axis during early pregnancy - Hanting Xu; Fangyuan Chen; Zhihao Liu; Rufei Gao; Junlin He; Fangfang Li; Nanyan Li; Xinyi Mu; Taihang Liu; Yingxiong Wang; Xuemei Chen (Environmental Research, 2024)

Spatiotemporal variations of extreme weather events and climate drivers in the Three Gorges Reservoir Area and its surrounding regions from 1960 to 2020 - Zikang Ren; Huarong Zhao; Xinzhi Mu; Qinxue Xu; Kangming Shi; Guoliang Yang (Atmospheric Research, 2024)

Transcriptomic and physiological analysis provide new insight into seed shattering mechanism in Pennisetum alopecuroides ‘Liqiu’ - Yue Xu; Lingyun Liu; Ming Jia; Ke Teng; Na Mu; Yidi Guo; Muye Liu; Juying Wu; Wenjun Teng; Linkai Huang; Xifeng Fan; Yuesen Yue (Theoretical and Applied Genetics, 2024)

Spatial correlations in time and frequency domains between chlorophyll-a concentration and environmental factors in the Bohai Sea - Wan Xu; Di Mu; Zhenteng Yang; Dekui Yuan (Journal of Oceanology and Limnology, 2024)

Characterization of cotinine degradation in a newly isolated Gram-negative strain Pseudomonas sp. JH-2 - Kexin Wang; Lu Xu; Jiale Ma; Ying Zhou; Yinhu Jiang; Jie Zha; Yanqiu Cai; Jian He; Jiandong Jiang; Jiguo Qiu; Yang Mu (Archives of Microbiology, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Effects of the Lactiplantibacillus plantarum YB-106 and Leuconostoc mesenteroides YB-23 strains on the quality and microbial diversity of spicy cabbage - Weichao Liu; Lixuan Chang; Yunpeng Xu; Tingting Shan; Guangqing Mu; Fang Qian (International Journal of Food Microbiology, 2024)

Effects of Lacticaseibacillus paracasei XJ-003 on the allergenicity and antigenicity of milk proteins during fermentation - Yunpeng Xu; Feifei Zhang; Ruida Ma; Zhao Zhang; Lei Chi; Yue Li; Chao Xu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2024)

Efficient Cr(VI) remediation by electrospun composite porous nanofibers incorporating biomass with metal oxides and metal-organic framework - Ronggang Luo; Ruiqi Li; Zhangzhi Zheng; Lianpeng Zhang; Linkun Xie; Chunhua Wu; Siqun Wang; Xijuan Chai; Nyuk Ling Ma; Mu. Naushad; Guanben Du; Kaimeng Xu (Environmental Pollution, 2024)

Engineering the substrate acceptance of l-amine dehydrogenase enables the collective biocatalytic synthesis of N-heterocyclic primary amines - Tao Wu; Yan Xu; Yao Nie; Xiaoqing Mu (Chemical Engineering Journal, 2024)

Effect of vegetation restoration type and topography on soil water storage and infiltration capacity in the Loess Plateau, China - Dexun Qiu; Ruirui Xu; Peng Gao; Xingmin Mu (CATENA, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Pretreatment with rumen fluid improves methane production in the anaerobic digestion of corn straw - Fenglian Xu; Lan Mu; Yifan Wang; Hao Peng; Junyu Tao; Guanyi Chen (Fuel, 2024)

A review of fructosyl-transferases from catalytic characteristics and structural features to reaction mechanisms and product specificity - Wei Xu; Xiaoqi Zhang; Dawei Ni; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Chemistry, 2024)

Revolutionary MOF-enhanced anion exchange membrane for precise monovalent anion separation through structural optimization and doping - Junhua Li; Zhipeng Xu; Junbin Liao; Edison Huixiang Ang; Xuanhua Chen; Junjie Mu; Jiangnan Shen (Desalination, 2024)

Fabrication of a straw-based degradable mulch film with magnetically controlled-release glyphosate - Dongqing Cai; Mengjia Cui; Linying Wang; Jinghong Ye; Xianghai Kong; Ruobing Mu; He Xu; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2024)

Utilizing soil organic phosphorus for sustainable crop production: insights into the rhizosphere - Kai Zhang; Dongfang Zheng; Yu Gu; Jie Xu; Maoying Wang; Bo Mu; Sijie Wen; Tao Tang; Zed Rengel; Jianbo Shen (Plant and Soil, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Factors affect the oxygen production of Chlorella pyrenoidosa in a bacterial-algal symbiotic system: Light intensity, temperature, pH and static magnetic field - Shiyu Yin; Wenbiao Jin; Tingting Xi; Xu Zhou; Zhongqi He; Xuli Meng; Mu. Naushad; Guangming Jiang; Xuan Li (Process Safety and Environmental Protection, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Oxygen-vacancy-tunable mesocrystalline ZnO twin "cakes" heterostructured with CdS and Cu nanoparticles for efficiently photodegrading sulfamethoxazole - Wuwu Mu; Minghui Xu; Xiaofeng Sun; Guorong Liu; Hua Yang (Journal of Environmental Chemical Engineering, 2024)

Gelatin films reinforced by tannin-nanocellulose microgel with improved mechanical and barrier properties for sustainable active food packaging - Min Li; Lukuan Guo; Yongxiang Mu; Xiaodi Huang; Liqiang Jin; Qinghua Xu; Yulu Wang (Food Hydrocolloids, 2024)

The key proteolytic enzyme analysis of industrial Aspergillus oryzae at solid-state koji fermentation with a local database extension - Yali Mu; Yueshu Li; Yumei Wu; Dong Wang; Lijie Zhang; Yan Xu (Food Bioscience, 2024)

Member separation and deformation recognition of spatial grid structures in-service - Mu-Nan Xu; Li-Min Sun; Yu-Fei Liu; Bao-Luo Li; Meng Zhou; Xuan Chen (Engineering Structures, 2024)

Preparation of iron oxide-modified digestate biochar and effect on anaerobic digestion of kitchen waste - Yifan Wang; Lan Mu; Chen Chen; Fenglian Xu; Hao Peng; Yingjin Song; Guanyi Chen (Bioresource Technology, 2024)

Changes in sources and formation mechanisms of carbonaceous aerosols driven by short-term air pollution controls in Megacity Xi'an, China - Zimeng Zhang; Tong Sha; Zhen Mu; Jinwen Li; Zipeng Dong; Dyussenova Ainur; Jiale Ding; Xingxing Jiang; Tengfei Xu; Qingcai Chen (Atmospheric Environment, 2024)

Lactiplantibacillus plantarum DLPT4 Protects Against Cyclophosphamide-Induced Immunosuppression in Mice by Regulating Immune Response and Intestinal Flora - Yinglong Song; Mengying Sun; Fenglian Ma; Dongxue Xu; Guangqing Mu; Yang Jiao; Ping Yu; Yanfeng Tuo (Probiotics and Antimicrobial Proteins, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Development and application of greenhouse light environment simulation technology based on light path tracing - Zhihui Mu; Yu Bo; Jihang Xu; Kai Song; Boda Dong; Jian Wang; Sheng Shu; Yu Wang; Shirong Guo (Computers and Electronics in Agriculture, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

A framework to identify failure scenarios in the control mode transition process for autonomous ships with dynamic autonomy - X. Yang; T. Zhou; X.Y. Zhou; W.J. Zhang; C.R. Mu; S. Xu (Ocean & Coastal Management, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

A constrained 3D gravity inversion for complex density distributions: Application to Brazil rifted continental margin - Xianzhe Yin; Changli Yao; Junlu Wang; Wenqiang Xu; Yuanman Zheng; Zelin Li; Wenrui Mu (Tectonophysics, 2024)

Multiple isotopes decipher the nitrogen cycle in the cascade reservoirs and downstream in the middle and lower Yellow River: Insight for reservoir drainage period - Jinglong Mu; Shuai Ding; Su Mei Liu; Guodong Song; Xiaoyan Ning; Xiaotong Zhang; Wenqi Xu; Hongmei Zhang (Science of The Total Environment, 2024)

Development of an alternative low-cost culture medium for a new isolated high-production DHA strain using kitchen wastewater - Qing Wang; Wenbiao Jin; Yujia Qin; Xu Zhou; Wei Han; Shuhong Gao; Xuan Li; Mu. Naushad; Guangming Jiang; Huan Liu (Process Safety and Environmental Protection, 2024)

Physiological and transcriptomic response reveals new insight into manganese tolerance of Celosia argentea Linn. - Liyun Liang; Mu Ze; Jun Yang; Qian Xu; Cunmei Du; Xiaohong Hu; Ming Dong; Lijuan Zou; Tuo Qi (Journal of Hazardous Materials, 2024)

Microbial dextran-hydrolyzing enzyme: Properties, structural features, and versatile applications - Ziwei Chen; Jiajun Chen; Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2024)

Production, effects, and applications of fructans with various molecular weights - Dawei Ni; Shuqi Zhang; Xiaoyong Liu; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2024)

Dual-use ionization source for direct and sensitive detection of trace carbamates residue - Tong Liu; Guodong Mu; Muyi He; Fengming Chen; Xiuli Xu; Feng Zhang (Food Chemistry, 2024)

Identification and application of a novel deoxynivalenol-degrading enzyme from Youhaiella tibetensis - Yan Shi; Wei Xu; Dawei Ni; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Chemistry, 2024)

Genetically engineering of Saccharomyces cerevisiae for enhanced oral delivery vaccine vehicle - Baoquan Han; Feng Yue; Xiaojun Zhang; Kun Xu; Zhiying Zhang; Zhongyi Sun; Lu Mu; Xiaoyu Li (Fish & Shellfish Immunology, 2024)

Facile method constructed naphthalene and Cu-C/Ni-C modified amorphous boron with high ignition and combustion performances - Taizhong Huang; Siyu Xu; Heng Li; Hanyu Jiang; Yanlu Mu; Ergang Yao; Xinyu Zhu; Fengqi Zhao (Chemical Engineering Journal, 2024)

A bibliometric assessment of the science and practice of blue–green space (BGS): hot spots, lacunae, and opportunities - Bo Mu; Ruting Zhao; Yang Liu; Enkai Xu; Yali Zhang; Hong Wei; Guohang Tian (Socio-Ecological Practice Research, 2024)

Sea level rise along China coast from 1950 to 2020 - Dapeng Mu; Tianhe Xu; Haoming Yan (Science China Earth Sciences, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Recent progress in health effects and enzymatic production of epilactose, a functional lactose derivative - Suchun Xiong; Zhaolin Huang; Wei Xu; Junmei Ding; Dawei Ni; Wanmeng Mu (Trends in Food Science & Technology, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Improving thermostability, solvent tolerance, and reusability of methyl parathion hydrolase through immobilization into the metal-organic framework ZIF-8 - Wei Xu; Minwen Sun; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Bioscience, 2024)

Modeling the effects of land use/land cover changes on river runoff using SWAT models: A case study of the Danjiang River source area, China - Weichao Liu; Jianhua Wu; Fei Xu; Dawei Mu; Pengbin Zhang (Environmental Research, 2024)

Corrigendum to “Mussel-inspired polysaccharide-based sponges for hemostasis and bacteria infected wound healing” [Carbohydrate Polymers. 295 (2022) 119868] - Wen Sun; Changjun Mu; Xu Zhang; Hengchong Shi; Qiuyan Yan; Shifang Luan (Carbohydrate Polymers, 2024)

FTO overexpression expedites wound healing and alleviates depression in burn rats through facilitating keratinocyte migration and angiogenesis via mediating TFPI-2 demethylation - Zihan Xu; Xiumei Zhu; Shengzhi Mu; Ronghui Fan; Benfeng Wang; Wenjie Gao; Tao Kang (Molecular and Cellular Biochemistry, 2024)

Identification of the Spatiotemporal Variability and Pollution Sources for Potential Pollutants of the Malian River Water in Northwest China Using the PCA-APCS-MLR Receptor Model - Dawei Mu; Jianhua Wu; Xiaofei Li; Fei Xu; Yongqiang Yang (Exposure and Health, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Comparative evaluation of soybean meal vs. extruded soybean meal as a replacer for fishmeal in diets of olive flounder (Paralichthys olivaceus): Effects on growth performance and muscle quality - Nannan Shen; Zhicheng Song; Cancan Xia; Hua Mu; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Yongkai Sun; Chaoqing Wei; Lu Zhang (Aquaculture, 2024)

Biogeography and diversity patterns of functional genes associated with C, N, P, S cycling processes across China classical sea sediments - Shuai Liu; Xin Huang; Hongyu Mu; Minggang Zheng; Shaoping Kuang; Hui Chen; Yan Xu; Dong Wang; Huan Liu; Xuan Li (Science of The Total Environment, 2024)

Impacts of seasonality, drought, nitrogen fertilization, and litter on soil fluxes of biogenic volatile organic compounds in a Mediterranean forest - Kaijun Yang; Joan Llusià; Catherine Preece; Roma Ogaya; Laura Márquez Tur; Zhaobin Mu; Chengming You; Zhenfeng Xu; Yu Tan; Josep Peñuelas (Science of The Total Environment, 2024)

Preparation of chromium oxide by hydrothermal reduction of sodium chromate aqueous solution with hydrogen and application to chromite ore processing - Panpan Mu; Hongling Zhang; De'an Pan; Shuting Liang; Taiping Lou; Hongbin Xu (Hydrometallurgy, 2024)

Deoxynivalenol: Occurrence, toxicity, and degradation - Yulei Zhang; Binbin Ouyang; Wenli Zhang; Cuie Guang; Wei Xu; Wanmeng Mu (Food Control, 2024)

Semiconductor nanosheets for electrocatalytic self-coupling of benzaldehyde to hydrobenzoin - Li Gong; Chao Yue Zhang; Xiao Mu; Xu Han; Junshan Li; Jordi Arbiol; Jin Yuan Zhou; Tanja Kallio; Paulina R. Martínez-Alanis; Andreu Cabot (Chemical Engineering Journal, 2024)

Relative humidity and solar radiation exacerbate snow drought risk in the headstreams of the Tarim River - Zhixia Wang; Shengzhi Huang; Zhenxia Mu; Guoyong Leng; Weili Duan; Hongbo Ling; Jia Xu; Xudong Zheng; Pei Li; Ziyan Li; Wenwen Guo; Yifei Li; et al. (Atmospheric Research, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Abundance, characteristics and risk assessment of microplastics in aquatic sediments: A comparative study in the Yellow River and Yellow Sea - Shuai Liu; Hairong You; Hongyu Mu; Jiaxin Cheng; Shaoping Kuang; Fayuan Wang; Hui Chen; Minggang Zheng; Yan Xu; Tao Liu (Waste Management, 2023)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

Sustainable development of the mining sector for achieving common prosperity in Chinese rural areas - Yiru Chen; Mu He; Yi Xu (Resources Policy, 2023)

Evaluation of long-term spatio-temporal characteristics of water and nitrogen in the vadose zone and potential threats to groundwater under different irrigation strategies - Jiatun Xu; Qing Mu; Shikun Sun; Nan Yang; Xiongbiao Peng; Yufeng Zou; Shaoyuan Feng; Huanjie Cai (Journal of Cleaner Production, 2023)

Multi-objective optimization of gas-steam-power system for an integrated iron and steel mill considering carbon emission reduction and cost - Tingting Xu; Zhaoyi Huo; Tong Wang; Jiawei Lv; Yixuan Han; Lin Mu (Journal of Cleaner Production, 2023)

An esterase activity-based biosensor for rapid and sensitive detection of viable Escherichia coli O157:H7 in milk - Xiaoyan Feng; Donggen Zhou; Dan Mu; Hengyi Xu (International Dairy Journal, 2023)

Low temperature preparation of high-performance citric acid crosslinked starch gels with adjustable properties based on cationic esterification synergistic crosslinking - Wenguang Wei; Min Wu; Nan Shang; Rongyi Mu; Tong Zhang; Huihuang Xu (Food Hydrocolloids, 2023)

An overview of chemical, physical and biological methods for zearalenone elimination: Recent advances and future prospective - Yulei Zhang; Binbin Ouyang; Wenli Zhang; Cuie Guang; Wei Xu; Wanmeng Mu (Food Control, 2023)

Oxalic acid-enhanced sulfamethoxazole degradation by V2O3/percarbonate process: Insights into the reactive oxygen species generation and conversion - Rui Liu; Mu-cheng Xu; Jin-yan Yang (Chemical Engineering Journal, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

Groundwater Quality Assessment Using EWQI With Updated Water Quality Classification Criteria: A Case Study in and Around Zhouzhi County, Guanzhong Basin (China) - Yongqiang Yang; Peiyue Li; Vetrimurugan Elumalai; Jing Ning; Fei Xu; Dawei Mu (Exposure and Health, 2023)

Residue dissipation dynamics and dietary risk assessment of emamectin benzoate, chlorantraniliprole, chlorfenapyr, and lufenuron in cabbage - Xiaoyao Wang; Shuai Hu; Lingtao Meng; Kai Wang; Xianxia Zhang; Ke Li; Ning Wang; Nan Zou; Yue Xu; Beixing Li; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2023)

Effect mechanism of iron conversion on adsorption performance of hydrochar derived from coking sludge - Jun Zhong; Wei Zhu; Xin Wang; Jipeng Sun; Biao Mu; Yucheng Xu; Guorui Li (Science of The Total Environment, 2023)

Thermokarst lake changes along the Qinghai-Tibet Highway during 1991–2020 - Mei Mu; Cuicui Mu; Pengsi Lei; Xiaoxiao Mo; Yuan Qiao; Xu Chen; Hebin Liu (Geomorphology, 2023)

Characteristics of secondary inorganic aerosols and contributions to PM2.5 pollution based on machine learning approach in Shandong Province - Tianshuai Li; Qingzhu Zhang; Xinfeng Wang; Yanbo Peng; Xu Guan; Jiangshan Mu; Lei Li; Jiaqi Chen; Haolin Wang; Qiao Wang (Environmental Pollution, 2023)

Mesoporous SiO2 anode armour for lithium oxygen battery - Hailiang Mu; Kun Luo; Yaming Pang; Xiangqun Zhuge; Zhengping Ding; Yurong Ren; Degui Li; Zhihong Luo; Ben Bin Xu; Maryam Bayati; Xiaoteng Liu (Chemical Engineering Journal, 2023)

Theoretical Analysis of Plastic Behavior of Sandwich Beam with Metal Foam under Repeated Impacts - Kailing Guo; Mengying Mu; Wei Cai; Bofang Xu; Ling Zhu (Journal of Marine Science and Engineering, 2023)
The phenomenon of repeated impacts on engineering structures is very common, especially in naval and ocean engineering. When marine structures are subjected to repeated impact loadings, deformation and damage will accumulate as the impact number increases, resulting in the failure and damage of the structures, even causing serious accidents. Based on the rigid-plastic assumption, a theoretical model is established to analyze the plastic mechanical behavior of metal foam sandwich beams (MFSBs) suffering from repeated impacts, in which the membrane factor method (MFM) is applied to derive analytical solutions for the plastic responses of MFSBs. The theoretical predictions agree well with the results of impact tests and numerical simulations, indicating that the theoretical model is accurate and reliable. In addition, the dynamic responses of MFSBs are analyzed based on the MFM, and the effects of the core strength and the face thickness on the deflection responses are determined. The results show that the dimensionless permanent deflection of MFSBs is sensitive to the core strength ratio and the face thickness ratio, and as the core strength ratio or the face thickness ratio increases, the dimensionless permanent deflection decreases gradually in an exponential form. In addition, the influence of the core strength ratio and face thickness ratio becomes more significant as the impact number increases. The proposed theoretical method can provide a theoretical reference and technical support for the design of metal foam sandwich structures with improved impact resistance under repeated impact loadings.

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

Chaste honey in long term-storage: Occurrence and accumulation of Maillard reaction products, and safety assessment - Sha Yan; Min Zhang; Yuzhe Yuan; Guodong Mu; Haitao Xu; Tian Zhao; Yinchen Wang; Xiaofeng Xue (Food Chemistry, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

Metabolic degradation of polysaccharides from Lentinus edodes by Kupffer cells via the Dectin-1/Syk signaling pathway - Yu Zhang; Wenqi Tang; Ziming Zheng; Gang Nie; Yuxue Zhan; Xu Mu; Yuxuan Liu; Kaiping Wang (Carbohydrate Polymers, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Bioaccumulation and elimination, acute toxicity analysis and risk assessment of diflubenzuron in common carp (Cyprinus carpio) - Lu Qiao; Lu Chen; Zhen Yang; Jinhua Xu; Jinlong Song; Xingyang Li; Huiwu Sun; Yingchun Mu (Chemosphere, 2023)

Degradation of tetracyclines via calcium peroxide activation by ultrasonic: Roles of reactive species, oxidation mechanism and toxicity evaluation - Zujun Xu; Shaofang Sun; Mingchang Gao; Ruibin Zheng; Haotian Mu; Liping Qiu; Jun Ma (Chemosphere, 2023)

Biological characters identification for hard clam larva based on the improved YOLOX-s - Yaxin Wang; Haiyun Wu; Xiuping Hua; Dongyue Ren; Yang Li; Zhimin Mu; Wei Xu; Yong Wei; Tao Zhang; Yongcheng Jiang (Computers and Electronics in Agriculture, 2023)

Fabrication and optimization of passive flexible ammonia sensor for aquatic supply chain monitoring based on adaptive parameter adjustment artificial neural network (APA-ANN) - Jinchao Xu; Boyu Mu; Luwei Zhang; Rong Chai; Yanfu He; Xiaoshuan Zhang (Computers and Electronics in Agriculture, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Numerical study on the VIVs of two side-by-side elastically coupled cylinders under different Re and natural frequencies - Guangjun Liu; Zhiyou Song; Wanhai Xu; Mu Sha (Ocean Engineering, 2023)

Multi-omics reveals 2-bromo-4,6-dinitroaniline (BDNA)-induced hepatotoxicity and the role of the gut-liver axis in rats - Fuchang Deng; Guangqiu Qin; Yuanyuan Chen; Xu Zhang; Mu Zhu; Min Hou; Qiao Yao; Wen Gu; Chao Wang; Hui Yang; Xudong Jia; Chongming Wu; et al. (Journal of Hazardous Materials, 2023)

Assessing the timing and the duration of exposure to air pollution on cardiometabolic biomarkers in patients suspected of coronary artery disease - Kexin Zhu; Zhihui Hou; Conghong Huang; Muwu Xu; Lina Mu; Guan Yu; Joel D. Kaufman; Meng Wang; Bin Lu (Environmental Research, 2023)

Changes in mean and extreme homogeneous precipitation in China during 1960–2020 - Yanjuan Wu; Hongli Mu; Shuang-ye Wu; Yu Xu; Ming Xu; Huawu Wu; Robin T. Clark; Chao Gao (Atmospheric Research, 2023)

D-allulose, a versatile rare sugar: recent biotechnological advances and challenges - Wenli Zhang; Ding Chen; Jiajun Chen; Wei Xu; Qiuming Chen; Hao Wu; Cuie Guang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2023)

Silibinin exerts neuroprotective effects against cerebral hypoxia/reoxygenation injury by activating the GAS6/Axl pathway - Weiping Li; Zhe Zhang; Jiawen Li; Jun Mu; Meng Sun; Xue Wu; Xiaochen Niu; Yang Yang; Huanle Yan; Xiaoling Xu; Chengxu Xue; Lu Qian; et al. (Toxicology, 2023)

Maximizing jet fuel production from n-hexadecane hydrocracking over Pt-supported Y catalysts: Importance of ideal hydrocracking characteristics - Yi Li; Chao Mu; Guangxin Chu; Yule Wang; Jing Xu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Aspirin alleviates cisplatin-induced acute kidney injury through the AMPK-PGC-1α signaling pathway - Danning Tong; Enshuang Xu; Ruidong Ge; Mengxin Hu; Shengzi Jin; Jing Mu; Yun Liu (Chemico-Biological Interactions, 2023)

Proteomic analysis reveals mechanisms of mixed wastewater with different N/P ratios affecting the growth and biochemical characteristics of Chlorella pyrenoidosa - Xinrui Mao; Xu Zhou; Xiumin Fan; Wenbiao Jin; Jingjing Xi; Renjie Tu; Mu. Naushad; Xuan Li; Huan Liu; Qilin Wang (Bioresource Technology, 2023)

Molecular characterization of a novel ambiguivirus isolated from the phytopathogenic fungus Setosphaeria turcica - Jichun Jia; Xu Chen; Xue Wang; Xu Liu; Nuo Zhang; Baojun Zhang; Yindong Chang; Fan Mu (Archives of Virology, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Quantifying climate and anthropogenic impacts on runoff using the SWAT model, a Budyko-based approach and empirical methods - Ruirui Xu; Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Wenyi Sun; Peng Gao (Hydrological Sciences Journal, 2023)

Visualizing sub-layer structural transformation in carbonized wood tracheid by Raman mapping - Jingjing Xiong; Binbin Xu; Bin Zhang; Peng Jiang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Genome-Wide DNA Methylation Dynamics During Drought Responsiveness in Tibetan Hulless Barley - Dunzhu Jiabu; Mingzhai Yu; Qijun Xu; Haizhen Yang; Wang Mu; Yuzhen Basang (Journal of Plant Growth Regulation, 2023)
Differences in drought stress tolerance within diverse grass genotypes have been attributed to epigenetic modifications. DNA methylation is an important epigenetic alteration regulating responses to drought stress. However, its effects on drought tolerance are poorly understood in Tibetan hulless barley. Here, bisulfite sequencing was conducted to profile the DNA methylation patterns of drought-tolerant variety (XL) and drought-sensitive (DQ) under drought and control conditions. A total of 5843 million reads were generated. We found the significant genome-wide changes in CHH methylation rates between XL and DQ, while CG or CHG methylation rates did not. Besides that, the two contrasting varieties do reveal distinct responses to drought stress in antioxidant activities and differentially methylated regions (DMRs). Genes in drought-tolerant varieties XL are rapidly and significantly methylated when exposed to drought stimulus. These DMRs-related genes in XL are significantly enriched in defense response and response to stimuli via gene-ontology enrichment analysis. Then, we focused on 1003 transcription factors and identified 15 specific DMRs-related transcription factors exhibiting specific methylation changes under drought stimuli. Finally, we identified three DMRs-related TFs ( HvRR12, HvRR2, and HvCSP41B ), where Arabidopsis homologs involve in responses to drought conditions. Altogether, abiotic stresses could be rapidly respond and mediated by methylation of transcription factors in hulless barely.

Ecological risk assessment of pesticides on soil biota: An integrated field-modelling approach - Hongyu Mu; Xiaomei Yang; Kai Wang; Darrell Tang; Wen Xu; Xuejun Liu; Coen J. Ritsema; Violette Geissen (Chemosphere, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Metagenomic analysis to determine the characteristics of antibiotic resistance genes in typical antibiotic-contaminated sediments - Han Yang; Mu Xu; Liqing Wang; Xianyun Wang; Erik Jeppesen; Wei Zhang (Journal of Environmental Sciences, 2023)

Engineering D-allulose 3-epimerase from Clostridium cellulolyticum for improved thermostability using directed evolution facilitated by a nonenzymatic colorimetric screening assay - Jiajun Chen; Zhaolin Huang; Ting Shi; Dawei Ni; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2023)

Membrane with horizontally rigid zeolite nanosheet arrays against zinc dendrites in zinc-based flow battery - Yongsheng Xia; Xiaoxuan Hou; Xinyi Chen; Feiyan Mu; Yan Wang; Liheng Dai; Xin Liu; Ying Yu; Kang Huang; Weihong Xing; Zhi Xu (Chemical Engineering Journal, 2023)

Derivation and validation of soil cadmium thresholds for the safe farmland production of vegetables in high geological background area - Demiao Mu; Shunan Zheng; Dasong Lin; Yingming Xu; Ruyin Dong; Penggang Pei; Yuebing Sun (Science of The Total Environment, 2023)

Dependence assessment in human reliability analysis using the 2-tuple linguistic information and DEMATEL method - Fei Gao; Wenjiang Liu; Xu Mu; Wenhao Bi; An Zhang (Process Safety and Environmental Protection, 2023)

Experimental study on the explosion destructive ability of magnesium powder/hydrogen hybrids in large space - Xinyu Xiong; Kai Gao; Jie Mu; Changquan Ji; Bin Li; Dan Zhang; Yadong Xu; Lifeng Xie (Process Safety and Environmental Protection, 2023)

Experimental and numerical investigation of the dynamic responses of longline aquacultural structures under waves - Wenwan Cheng; Yuanyuan Xu; Ping Mu (Ocean Engineering, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Effects of grouting cycle and aeration on sand strengthening with ureolytic bacteria - J. Xu; B. Mu; J. Chen; J. Zuo (International Journal of Environmental Science and Technology, 2023)

Light Intensity and Photoperiod Interaction Affects the Survival, Development, Molting and Apoptosis-Related Genes of Swimming Crab Portunus trituberculatus Larvae - Yun Zhao; Juan Dou; Hanying Xu; Zhen Ma; Yangfang Ye; Changkao Mu; Weiwei Song; Zhiming Ren; Chunlin Wang; Ce Shi (Fishes, 2023)
A 19-day experiment was conducted to investigate the optimal light intensity and photoperiod combination for larval swimming crabs Portunus trituberculatus in terms of survival, development, and apoptosis-related gene expression. Two photoperiods, i.e., 12 and 18 h photophases, and three light intensities, i.e., 126.08, 173.17, and 191.53 μmol m−2 s−1, were used in the study. The results showed that the cumulative survival rate (CSR) of larvae decreased with the increasing light intensity, and the adverse effect of high light intensity was only observed in long photophase groups. On the contrary, a long photophase and low light intensity elevated the CSR from zoea III to juvenile crabs. A long photophase also accelerated the development of zoea III larvae and upregulated the molting-related (ecr and rxr) and apoptosis-related (jnk, p53, and bcl-2) gene expressions. Taken together, the present study suggested that the light intensity and the photoperiod had a combined effect on P. trituberculatus larvae. The optimal light intensity and photoperiod for P. trituberculatus larvae were 126.08 μmol m−2 s−1 and an 18 h photophase, respectively.

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

Popcorn-based dual-monomer copolymerized temperature/pH-sensitive core-shell hydrogels - Wenxu Zhang; Xuyang Mu; Yan Xu; Sijie Li; Xiaoming Liu; Ziqiang Lei (Journal of Environmental Chemical Engineering, 2023)

Modification of sedimentation and bioaccumulation behavior as an efficient strategy to modulate the toxicity of pyraclostrobin to zebrafish (Danio rerio) - Aiping Wang; Yue Sun; Zhengyi Sun; Xiao Liu; Xin Yu; Ke Li; Xianxia Zhang; Yue Xu; Wei Mu; Beixing Li (Environmental Pollution, 2023)

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

Rational fabrication of completely amorphous chitosan-formyl-sucrose sorbents with excellent durability and regenerability for high-throughput dye removal - Bingnan Mu; Lan Xu; Yiqi Yang (Chemical Engineering Journal, 2023)

Basal Forebrain Cholinergic Innervation Induces Depression-Like Behaviors Through Ventral Subiculum Hyperactivation - Nana Yu; Huina Song; Guangpin Chu; Xu Zhan; Bo Liu; Yangling Mu; Jian-Zhi Wang; Yisheng Lu (Neuroscience Bulletin, 2023)
Malfunction of the ventral subiculum (vSub), the main subregion controlling the output connections from the hippocampus, is associated with major depressive disorder (MDD). Although the vSub receives cholinergic innervation from the medial septum and diagonal band of Broca (MSDB), whether and how the MSDB-to-vSub cholinergic circuit is involved in MDD is elusive. Here, we found that chronic unpredictable mild stress (CUMS) induced depression-like behaviors with hyperactivation of vSub neurons, measured by c-fos staining and whole-cell patch-clamp recording. By retrograde and anterograde tracing, we confirmed the dense MSDB cholinergic innervation of the vSub. In addition, transient restraint stress in CUMS increased the level of ACh in the vSub. Furthermore, chemogenetic stimulation of this MSDB-vSub innervation in ChAT - Cre mice induced hyperactivation of vSub pyramidal neurons along with depression-like behaviors; and local infusion of atropine, a muscarinic receptor antagonist, into the vSub attenuated the depression-like behaviors induced by chemogenetic stimulation of this pathway and CUMS. Together, these findings suggest that activating the MSDB-vSub cholinergic pathway induces hyperactivation of vSub pyramidal neurons and depression-like behaviors, revealing a novel circuit underlying vSub pyramidal neuronal hyperactivation and its associated depression.

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Artificial intelligence-aided preparation of perovskite SrFexZr1-xO3-δ catalysts for ozonation degradation of organic pollutant concentrated water after membrane treatment - Xu Wang; Yanan Zhang; Cheng Zhang; Huangzhao Wei; Haibo Jin; Zhao Mu; Xiaofei Chen; Xinru Chen; Ping Wang; Xiaoyan Guo; Fuchen Ding; Xiaowei Liu; et al. (Chemosphere, 2023)

Atmospheric dustfall exhibits consistent sedimentary sorting with height evidenced by grain size characteristics - Yongchong Lin; Guijin Mu; Xue Zhao; Lishuai Xu; Jifeng Zhang (Science of The Total Environment, 2023)

Short-term impacts of air pollution on the platelet-lymphocyte ratio and neutrophil-lymphocyte ratio among urban adults in China - Weihong Qiu; Heng He; Bin Wang; Dongming Wang; Ge Mu; Tao Xu; Min Zhou; Zi Ye; Jixuan Ma; Weihong Chen (Journal of Environmental Sciences, 2023)

Study on derived hydrogen and ignition influencing factors of moist magnesium debris - Xinyu Xiong; Kai Gao; Jie Mu; Changquan Ji; Bin Li; Dan Zhang; Yadong Xu; Lifeng Xie (Fuel, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

Seawall-induced impacts on large river delta wetlands and blue carbon storage under sea level rise - Liehui Zhi; Xiaowen Li; Junhong Bai; Dongdong Shao; Baoshan Cui; Yonglin Mu; Tiantian Ma; Xu Xie; Hazrat Bilal; Usman Abdullahi (Science of The Total Environment, 2023)

Considering spatio-temporal dynamics of soil water with evapotranspiration partitioning helps to clarify water utilization characteristics of summer maize under deficit irrigation - Jiatun Xu; Qing Mu; Yibo Ding; Shikun Sun; Yufeng Zou; Lianyu Yu; Pengyan Zhang; Nan Yang; Wei Guo; Huanjie Cai (Journal of Hydrology, 2023)

Ammonium-free and grain-protection deliming technology with the combination of aromatic sulfonic acid and sodium dihydrogen phosphate in leather manufacture - Chunxiao Zhang; Ting Liu; Baosheng Huang; Xu Zhang; Biyu Peng; Changdao Mu (Journal of Cleaner Production, 2023)

Selective absorption and efficient biodegradation of petroleum pollutants by oleophilic porous activated sludge loading with microorganism - Yuhan Zhang; Juanjuan Xu; Xiaoqian Jiang; Xiaotong Mu; Qimeige Hasi; Kaihui Xu; Guihua Li; Lihua Chen (Journal of Environmental Chemical Engineering, 2023)

Effects of vegetation restoration on soil infiltrability and preferential flow in hilly gully areas of the Loess Plateau, China - Dexun Qiu; Ruirui Xu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (CATENA, 2023)

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

Biomass-derived polyphosphazene toward simultaneously enhancing the flame retardancy and mechanical properties of epoxy resins - Yuling Xiao; Xiaowei Mu; Siqi Chen; Guangyong Jiang; Zhoumei Xu; Chao Ma; Lei Song; Yuan Hu (Chemosphere, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Spatial distribution characteristics and prediction of fluorine concentration in groundwater based on driving factors analysis - Mu-Yuan Lu; Yuan Liu; Gui-Jian Liu; Yong-Li Li; Jin-Zhao Xu; Guan-Yu Wang (Science of The Total Environment, 2023)

Experimental investigation on the mooring dynamics of the flexible trash intercept net under wave-current combined actions - Mingxiao Xie; Shan Li; Yu Mu; Yanjie Wei; Tiaojian Xu; Zhenxiang Sun; Chunguang Yuan (Ocean Engineering, 2023)

The textural properties of cooked convenience rice upon repeated freeze–thaw treatments are largely affected by water mobility at grain level - Shiyi Lu; Jie Li; Minghao Xu; Yifan Mu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2023)

Performance and mechanisms for tetrabromobisphenol A efficient degradation in a novel homogeneous advanced treatment based on S2O42− activated by Fe3+ - Wei Song; Mu Li; Sen Xu; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Wenhui Qiu; Zhihong Wang; Qi Song; Kalpana Bhatt; Caixia Fu (Environmental Pollution, 2023)

Exploring the organic solvent resistance of anion exchange membranes based on poly(2,6-dimethyl-1,4-phenyl oxide) for electrodialysis desalination - Junbin Liao; Jingwen Xu; Huimin Ruan; Junjie Mu; Xu Jie; Wei Li; Yanqing Xu; Jiangnan Shen (Desalination, 2023)

Dual functional mesoporous silica colloidal electrolyte for lithium-oxygen batteries - Hailiang Mu; Xiangqun Zhuge; Guogang Ren; Kun Luo; Zhengping Ding; Yurong Ren; Zhihong Luo; Maryam Bayati; Ben Bin Xu; Xiaoteng Liu (Chemical Engineering Journal, 2023)

Filling the gap between molecular and aggregate states: how does molecular packing affect photophysical properties? - Xu-Min Cai; Yuting Lin; Zhenguo Tang; Xuedan Zhang; Tianqi Mu; Shenlin Huang; Zheng Zhao; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Diosmetin inhibits subchondral bone loss and indirectly protects cartilage in a surgically-induced osteoarthritis mouse model - Hongzhi Ding; Huan Ding; Pei Mu; Xiongwei Lu; Zhixing Xu (Chemico-Biological Interactions, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

Recognizing and managing construction land reduction barriers for sustainable land use in China - Jia-He Zhou; Yu-Ming Zhu; Lei He; Hao-Jing Song; Bing-Xu Mu; Fen Lyu (Environment, Development and Sustainability, 2022)

A novel victorivirus isolated from the tobacco spot blight fungus Stagonosporopsis cucurbitacearum in China - Mengmeng Yang; Guiyao Wang; Wenjun Mu; Jianhua Guo; Jiaqin Xi; Liwei Hu; Kexin Liang; Qiang Xu; Zongyu Hu; Jizhen Song (Archives of Virology, 2022)

Effects of different photoperiods and feeding regimes on immune response, oxidative status, and tissue damage in juvenile rainbow trout (Oncorhynchus mykiss) - Hanying Xu; Ce Shi; Yangfang Ye; Changkao Mu; Chunlin Wang (Frontiers in Marine Science, 2022)
A three-month culture experiment was conducted to investigate the effects of the feeding regime on liver health, non-specific immunity, and apoptosis of juvenile rainbow trout under constant light conditions. A total of six experimental groups contained two photoperiods [LL (24L:0D) and LD (12L:12D)] and three feeding regimes [R (random feeding), D (mid-dark stage feeding), L (mid-light stage feeding)], defined as R-LL, D-LL, L-LL, R-LD, D-LD, L-LD. The experiment results revealed a significantly higher alanine aminotransferase (ALT) level in the nocturnal feeding group (D-LD) and significantly higher aspartate aminotransferase (AST) in the R-LL and D-LL groups, indicating possible liver damage in these groups. In addition, high serum levels of immunoglobulins M (IgM), complement 3 (C3), and complement 4 (C4) were observed in the LL (compared to LD), R (LL conditions), and D (LD conditions) groups, suggesting that stress may be present in these groups. Meanwhile, under LL, high cytokine genes ( tnf-α , il-1β , il-6 , and il-8 ) expression were observed in the liver and intestine of the L group, possibly reflecting a stronger immune response. In the liver, high malondialdehyde (MDA) content was observed in the LL (compared to LD), R (LD conditions), and D (LL conditions) groups, suggesting that these groups were subjected to oxidative damage. Further, higher apoptosis genes ( cytc and bcl-2 ) expression in the liver was detected in the R and D-LD groups. The highest level of hepatic apoptotic cells was also observed in the D-LD group. Taken together, long-term exposure to LL, random feeding, and nocturnal feeding can cause oxidative damage to juvenile rainbow trout, leading to hepatocyte apoptosis, while scheduled diurnal feeding can alleviate the oxidative damage caused by LL.

Astrocyte-derived lactate/NADH alters methamphetamine-induced memory consolidation and retrieval by regulating neuronal synaptic plasticity in the dorsal hippocampus - Xu Tan; Xiaoyu Liu; E Liu; Min Liu; Shouhong Mu; Zhaofang Hang; Weikai Han; Tingting Wang; Yang Zhang; Jing Zhang; Qingwei Yue; Jinhao Sun (Brain Structure and Function, 2022)

Photoperiod-independent diurnal feeding improved the growth and feed utilization of juvenile rainbow trout (Oncorhynchus mykiss) by inducing food anticipatory activity - Hanying Xu; Ce Shi; Yangfang Ye; Changkao Mu; Chunlin Wang (Frontiers in Marine Science, 2022)
A three-month culture experiment was designed to assess the effects of photoperiod and feeding regime on growth, feed utilization, and food anticipatory activity (FAA) of juvenile rainbow trout. The experiment included two photoperiods: 24L:0D (LL) and 12L:12D (LD); three feeding regimes: random feeding (R), mid-dark stage feeding (D), and mid-light stage feeding (L). A total of six treatment groups (R-LL, D-LL, L-LL, R-LD, D-LD, L-LD) were defined. The experimental results showed that the growth and feed utilization of the scheduled feeding groups (D and L groups) were significantly higher than those of the R group under both photoperiods, and there was no statistical difference between the D and L groups. A typical FAA was observed in the L group, independent of the photoperiod. Also, the digestive enzyme activity of the L group was synchronized by the feeding time under both photoperiods. There were rhythms in serum levels of glucose (GLU), triglyceride (TG), and total-cholesterol (T-CHO) in the D and L groups. Serum GLU also had a rhythm in the R group, but the peaks occurred at the feeding point (LL group) or after the feeding point (LD group), reflecting a possible passive rise in GLU after feeding. Serum cortisol was higher in the R group than in the scheduled feeding group, indicating that random feeding caused stress to juvenile rainbow trout. Serum insulin levels were found to increase before feeding in all three feeding regimes, probably reflecting the anticipation of food induced by the last meal. Serum melatonin levels were suppressed by the LL group. Serum 5-HT levels were synchronized by meal time in the R and L groups. Finally, rhythms of appetite-related genes were observed under all three feeding regimes, and more genes were rhythmic under LL, suggesting that food can strongly synchronize the feeding rhythm of juvenile rainbow trout when lacking light zeitgeber. In summary, this study concluded that diurnal feeding (L group) independent of photoperiod induced typical FAA in juvenile rainbow trout and that the LD (12L:12D) photoperiod and L (mid-light phase) feeding were recommended in the juvenile rainbow trout aquaculture.

Exotic fishes that are phylogenetically close but functionally distant to native fishes are more likely to establish - Meng Xu; Shao‐peng Li; Jaimie T. A. Dick; Dangen Gu; Miao Fang; Yexin Yang; Yinchang Hu; Xidong Mu (Global Change Biology, 2022)
Since Darwin's time, degree of ecological similarity between exotic and native species has been assumed to affect the establishment success or failure of exotic species. However, a direct test of the effect of exotic–native similarity on establishment of exotics is scarce because of the difficulty in recognizing failures of species to establish in the field. Here, using a database on the establishment success and failure of exotic fish species introduced into 673 freshwater lakes, we evaluate the effect of similarity on the establishment of exotic fishes by combining phylogenetic and functional information. We illustrate that, relative to other biotic and abiotic factors, exotic–native phylogenetic and functional similarities were the most important correlates of exotic fish establishment. While phylogenetic similarity between exotic and resident fish species promoted successful establishment, functional similarity led to failure of exotics to become established. Those exotic species phylogenetically close to, but functionally distant from, native fishes were most likely to establish successfully. Our findings provide a perspective to reconcile Darwin's naturalization conundrum and suggest that, while phylogenetic relatedness allows exotic fish species to pre‐adapt better to novel environments, they need to possess distinct functional traits to reduce competition with resident native fish species.

A Nonlinear Representation of Model Uncertainty in a Convective-Scale Ensemble Prediction System - Zhizhen Xu; Jing Chen; Mu Mu; Guokun Dai; Yanan Ma (Advances in Atmospheric Sciences, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

A transgene-free method for rapid and efficient generation of precisely edited pigs without monoclonal selection - Kui Xu; Xiuling Zhang; Zhiguo Liu; Jinxue Ruan; Changjiang Xu; Jingjing Che; Ziyao Fan; Yulian Mu; Kui Li (Science China Life Sciences, 2022)

Protecting Effect of Bacillus coagulans T242 on HT-29 Cells Against AAPH-Induced Oxidative Damage - Xiaoxi Gao; Yuhong Zhang; Guangqing Mu; Yunpeng Xu; Xinmiao Wang; Yanfeng Tuo; Fang Qian (Probiotics and Antimicrobial Proteins, 2022)

Photoperiod affects the survival rate but not the development of larval swimming crab Portunus trituberculatus - Hanying Xu; Juan Dou; Qingyang Wu; Yangfang Ye; Chunlin Wang; Changbin Song; Changkao Mu; Zhiming Ren; Ce Shi (Aquaculture International, 2022)

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Several major issues concerning the environmental transmission and risk prevention of SARS-CoV-2 - Jin Ma; Jian Xu; Xiaoli Zhao; Shouliang Huo; Xiaoli Duan; Yunsong Mu; Ying Wang; Yuan Wei; Jiang Chang; Xiaowei Jin; Fengchang Wu (Science China Earth Sciences, 2022)

Wood decay fungi: an analysis of worldwide research - Tong Li; Lizhen Cui; Xiufang Song; Xiaoyong Cui; Yulian Wei; Li Tang; Yanhong Mu; Zhihong Xu (Journal of Soils and Sediments, 2022)
Purpose Wood decay fungi are the only forms of life capable of degrading wood to its initial constituents, greatly contributing to the soil ecosystem. This study summarizes the current research status and development characteristics of global wood decay fungi research, in order to better understand their role in soils. Methods A bibliometric analysis was applied to the literature from 1913 to 2020, based on data from the Web of Science (WOS) Core Collection. For this, various bibliometric analysis methods, R (Biblioshiny package), and VOSviewer were applied. Results A total of 8089 documents in this field were identified in the WOS Core Collection. The annual number of publications tended to increase, with exponential growth after 2008. Researchers in this field were mainly concentrated in North Europe, the USA, and China. Biotechnology, applied microbiology, environmental sciences, and microbiology were the most popular WOS categories. Bioresource Technology and Applied Environmental Microbiology were the top two journals with the most citations. The top three authors with the most published papers were Dai YC, Martinez AT, and Cui BK. Co-occurrence analysis of author keywords identified six clusters, mainly divided into three categories: the classification and diversity, the degradation mechanisms, and the ecological functions of wood decay fungi. Clustering results further showed that the lignin degradation process and the application of wood decay fungi in industrial production and soil contamination remediation are current research hotspots. Conclusions We present a comprehensive and systematic overview of research related to wood decay fungi and provide a deep perspective to understand the associated research progress. This is important for facilitating the development of a profound understanding of the contribution of wood decay fungi to soil systems and the degradation of soil contaminants.

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Xiaoxin Dai; Lijun Qiu; Han Zhang; Chunying Xu; Bo Zhao; Yang Gao; Haidong Li; Yi Mu; Zhangjie Chu (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization, and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes were significantly decreased in the bisphenol A-exposed group, while the co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed, and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affects the mitochondrial respiratory chain in ovaries and may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols play a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.

Investigation of the Light Intensity Effect on Growth, Molting, Hemolymph Lipid, and Antioxidant Capacity of Juvenile Swimming Crab Portunus trituberculatus - Hanying Xu; Juan Dou; Qingyang Wu; Yangfang Ye; Changbin Song; Changkao Mu; Chunlin Wang; Zhiming Ren; Ce Shi (Frontiers in Marine Science, 2022)
An eight-week experiment was conducted to evaluate the effects of eight light intensities (0, 0.83, 1.61, 8.17, 15.89, 31.38, 63.69, and 124.31 μmol m -2 s -1 ) on the survival, growth, antioxidant, molting-related and apoptosis-related gene expression of juvenile swimming crab Portunus trituberculatus . The results showed that the survival rate of crabs was the highest under the light intensities of 8.17 and 15.89 μmol m -2 s -1 . Under this light intensity, the crabs had the lowest hemolymph glucose (GLU) but the highest triglyceride (TG) content. The crabs in these treatments also had the highest total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT) activities, and the lowest malondialdehyde (MDA) content. The growth performance (including weight gain and specific growth rate) and molting frequency of crabs increased with increasing light intensity. The improved growth performance and molting of 8.17 and 15.89 μmol m -2 s -1 groups were also accompanied by up-regulated of the retinoid-X receptor ( rxr ), ecdysone receptor ( ecr ), nuclear receptor E75 ( e75 ) gene expression, and down-regulated molt-inhibiting hormone ( mih ) gene expression. In addition, suboptimal light intensity (0, 0.83, 63.69, and 124.31 μmol m -2 s -1 ) significantly up-regulated the expression of apoptosis-related genes including c-Jun N-terminal kinase ( jnk ), tumor suppressor p53 ( p53 ), and B-cell lymphoma-2 ( bcl-2 ). Taken together, the suitable light intensity for the juvenile P. trituberculatus was estimated to be 9.96 μmol m -2 s -1 .

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

IgE Reactivity of Potential Allergens from the Swimming Crab Portunus trituberculatus and the Research of ELISA Reagent for Detecting Crab Food Anaphylaxis - Xueni Qiu; Qiongyan Zhou; Xiaoxia Zhu; Wei Lin; Changkao Mu; Ronghua Li; Yangfang Ye; Weiwei Song; Ce Shi; Lei Liu; Huan Wang; Chunlin Wang; et al. (Journal of Ocean University of China, 2022)

Native herbivores indirectly facilitate the growth of invasive Spartina in a eutrophic saltmarsh - Xiao Xu; Yan Zhang; Songshuo Li; Hongyang Chen; Mu Liu; Bo Li; Ming Nie (Ecology, 2022)
Current theory (e.g., consumer‐controlled theory) predicts that nutrient enrichment typically amplifies herbivory and thereby suppresses the growth and expansion of invasive plants. Herbivores can facilitate plant regrowth in the native community by stimulating complementary growth or ameliorating habitat conditions (e.g., by increasing soil oxygen and nutrient availability), but whether they have similar positive effects on invasive plants, especially under nutrient enrichment, remains unknown. Using a field nitrogen (N)‐enrichment × crab exclusion experiment, we evaluated and compared the effects of both N enrichment and crab herbivory on the growth performance of a global invasive cordgrass, Spartina alterniflora , and a co‐occurring native plant, Phragmites australis . We found that crabs consistently suppressed P. australis by density and aboveground biomass regardless of N enrichment. In contrast, for S. alterniflora , the negative effects of crabs under ambient N were replaced by positive effects under N enrichment, with crabs stimulating complementary increases in density and aboveground biomass. The differing effects between the N treatments were driven by crab burrowing activity, which increased soil N availability, and the nutrient‐use efficiency of S. alterniflora . Our findings revealed that native herbivores can have opposing effects on native and invasive plants, which broadens our understanding of how exotic plants can achieve dominance in a changing world.

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Long-term, multidomain analyses to identify the breed and allelic effects in MSTN-edited pigs to overcome lameness and sustainably improve nutritional meat production - Ziyao Fan; Zhiguo Liu; Kui Xu; Tianwen Wu; Jinxue Ruan; Xinmin Zheng; Shideng Bao; Yulian Mu; Tad Sonstegard; Kui Li (Science China Life Sciences, 2022)

Isoorientin suppresses sepsis-induced acute lung injury in mice by activating an EPCR-dependent JAK2/STAT3 pathway - Mu Hu; Jielai Yang; Yang Xu (Journal of Molecular Histology, 2022)

Expression and localization of amelotin, laminin γ2 and odontogenesis-associated phosphoprotein (ODAPH) on the basal lamina and junctional epithelium - Cong Li; Yan Gao; Zhenzhen Xu; Yuan Tian; Haiyu Mu; Cuicui Yu; Yuguang Gao; Li Zhang (Journal of Molecular Histology, 2022)

Varying growth rates of a marine eel, the whitespotted conger (Conger myriaster), are explained by the interaction between seasonal temperature and prey availability - Xiuxia Mu; Chongliang Zhang; Binduo Xu; Yupeng Ji; Ying Xue; Yiping Ren (Marine Biology, 2022)

Exploring the Occurrence Characteristics of Microplastics in Typical Maize Farmland Soils With Long-Term Plastic Film Mulching in Northern China - Jiajia Zhang; Guoyuan Zou; Xuexia Wang; Wencheng Ding; Li Xu; Baoyin Liu; Yunsen Mu; Xuran Zhu; Lianjie Song; Yanhua Chen (Frontiers in Marine Science, 2021)
Microplastics pollution has been threatening the global environmental security, in which agricultural activities are considered as a main source of microplastics occurrence in soils. However, little is known about the occurrence characteristics of microplastics in agricultural soils with long-term plastic film mulching. Therefore, the abundance, distribution, and composition of microplastics were investigated by analyzing 225 soil samples collected from typical maize ( Zea mays L.) planting zones with and without long-term (>20 years) plastic film mulching in northern China. Microplastics abundance in mulched soils (754 ± 477 items kg –1 ) was significantly higher than that in non-mulched soils (376 ± 149 items kg –1 ), which indicated that plastic film mulching contributed half of microplastics in soils. Moreover, microplastics abundance was significantly positively related to the length of time with film mulching applied. The percentage of microplastics <0.5 mm in mulched soils (50.9%) was significantly lower than that in non-mulched soils (62.2%). Microplastics abundance and size in mulched and non-mulched soils decreased with increased soil depth. Most microplastics were fragments of polypropylene, films of polyethylene, and fibers of polyester. The proportion of films in mulched soils was significantly higher than in non-mulched soils, whereas that of fibers was significantly higher in non-mulched soils. This study confirmed that long-term plastic film mulching increases microplastics pollution in agricultural soils, warranting further evaluation of the associated ecological risks of microplastics in soil ecosystems.

Grain size characteristics of the sand silt layers in the ancient delta of the dried Lop Nur lake (east Tarim Basin) and their environmental implications - Yongchong Lin; Guijin Mu; Lishuai Xu; Xue Zhao (Arabian Journal of Geosciences, 2021)

Lessons Learned from the Tragedy during the 100 km Ultramarathon Race in Baiyin, Gansu Province on 22 May 2021 - Qinghong Zhang; Chan-Pang Ng; Kan Dai; Jun Xu; Jian Tang; Juanzhen Sun; Mu Mu (Advances in Atmospheric Sciences, 2021)

Identification and functional analysis of a pollen fertility-associated gene GhGLP4 of Gossypium hirsutum L. - Hongli Zheng; Rongjia Wang; Qimeng Jiang; Diandian Zhang; Rongrong Mu; Yihan Xu; Vitalis E. Nnaemeka; Jun Mei; Yanyan Zhao; Fangfang Cai; Dongliang Yu; Yuqiang Sun; et al. (Theoretical and Applied Genetics, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Developing the non‐dimensional framework for water distribution formulation to evaluate sprinkler irrigation* - Ang Li; Xinyuan Mu; Xia Zhao; Jiamin Xu; Majid Khayatnezhad; Reza Lalehzari (Irrigation and Drainage, 2021)
Improving the application efficiency and leaching of solutes from the root zone in a sprinkler irrigation system are directly related to the uniformity of water distribution at the field surface. The coefficient of uniformity and distribution uniformity are affected by changes in wind speed and its direction, sprinkler characteristics and variations in operating pressure. The objective of this paper is to present modified equations for evaluating pressurized irrigation systems based on non‐dimensional infiltrated depths. The equations were obtained by four data groups including the average of the measured infiltration depths in any quarter. Coefficient of uniformity (CU), distribution uniformity (DU), application efficiency ( E a ) and deep percolation (DP) were used as performance indicators to evaluate the sprinkler irrigation system. The suggested method was compared to the existing approach to assess the evaluation indicators. Three data sets of observed information for wheel‐move, permanent solid set and semi‐solid set irrigation systems were collected in Chaharmahal and Bakhtiari provinces to evaluate the proposed formulation. Furthermore, the relationships between CU and DU were analysed for three scenarios of infiltration depth. Results show that the application efficiency was 12% less than previous equations because of using four average values.

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

Intraperitoneal injection of genistein affects the distribution and metabolism of cholesterol in female yellow catfish Tachysurus fulvidraco - Yushi Chen; Wenbin Xu; Qingji Zhang; Yilin Zhang; Ren Mu (Fish Physiology and Biochemistry, 2021)

Histopathological, hematological, and biochemical changes in high-latitude fish Phoxinus lagowskii exposed to hypoxia - Yuting Yang; Zhen Wang; Jing Wang; Fengming Lyu; Kexin Xu; Weijie Mu (Fish Physiology and Biochemistry, 2021)

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Sources of 24-h personal exposure to PM2.5-bound metals: results from a panel study in Wuhan, China - Xing Wang; Bin Wang; Lili Xiao; Xiuqing Cui; Xingzu Cen; Shijie Yang; Ge Mu; Tao Xu; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2021)

A ~ 230-year dust storm record from China’s Lake Gonghai on the northeast Loess Plateau - Lishuai Xu; Dejun Wan; Yonghong Duan; Yongchong Lin; Guijin Mu; Zhilei Zhen; Yongsheng Yang (Arabian Journal of Geosciences, 2021)

Whole-genome analysis of the trimethylation of histone H3 lysine 4 and lysine 27 in two contrasting Tibetan hulless barley genotypes under salinity stress - Basang Yuzhen; Zha Sang; Wang Mu; Mingzhai Yu; Yulin Wang; Hongjun Yuan; Qijun Xu (Acta Physiologiae Plantarum, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

QTL mapping and validation of bread wheat flag leaf morphology across multiple environments in different genetic backgrounds - Yang Tu; Hang Liu; Jiajun Liu; Huaping Tang; Yang Mu; Mei Deng; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2021)

A global analysis of enemy release and its variation with latitude - Meng Xu; Xidong Mu; Shuang Zhang; Jaimie T. A. Dick; Bingtao Zhu; Dangen Gu; Yexin Yang; Du Luo; Yinchang Hu (Global Ecology and Biogeography, 2021)
Aim The enemy release hypothesis (ERH) posits that exotic species suffer less enemy damage than natives, which promotes their successful invasion. However, the generality of less damage for exotics remains widely debated. A recent view proposes that enemy release (ER) could change systematically with latitude, potentially helping to explain these inconsistencies. Here, we test whether exotic plant species suffer consistently lower herbivore damage relative to natives and whether ER varies with latitude. Location Global. Time period 1960–2018. Major taxa studied Plants. Methods Using leaf herbivory data for 1,098 plant species, we compared the herbivory rate between exotic and native plants across all taxa, between the introduced and native range of exotic species and between exotic and native species co‐occurring in the same community. We tested the interaction effect between origin (exotic versus native) and latitude to assess variation in ER with latitude. We also examined whether the effect of origin and its interaction with latitude changed with plant growth form (woody versus non‐woody). Finally, based on two ER effect‐size datasets, two meta‐regressions were performed to demonstrate the relationship between ER and latitude. Results Leaf herbivory rates were commonly lower for exotics than for natives. However, this differential herbivory rate was significant only for woody plants. No significant interactions were found between origin and latitude, indicating that ER did not change with latitude. The meta‐regressions also demonstrated that ER was not significantly correlated with latitude. Main conclusions The widespread lower herbivory rate for exotic compared with native woody plant species supports the ERH for exotic woody plants. Consistent ER with latitude indicates that ER should play a similar role regardless of latitude. One future challenge is to assess the extent to which ER in woody exotic plants translates to performance advantages and thereby influences their invasion success.

Overexpression of LncRNA PSMG3-AS1 Distinguishes Glioblastomas from Sarcoidosis - Liusheng Chen; Guanliang Wang; Zihui Xu; Kailong Lin; Sen Mu; Yicheng Pan; Mengya Shan (Journal of Molecular Neuroscience, 2020)

Safety of azithromycin in pediatrics: a systematic review and meta-analysis - Linan Zeng; Peipei Xu; Imti Choonara; Zhenyan Bo; Xiangchen Pan; Wenyan Li; Xiaofeng Ni; Tao Xiong; Can Chen; Leshan Huang; Shamim Ahmad Qazi; Dezhi Mu; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromycin and placebo or other antibiotics using meta-analysis of RCTs. Results We included 133 studies with 4243 ADRs reported in 197,675 neonates, infants, and children who received azithromycin. The safety of azithromycin as MDA in pediatrics was poorly monitored. The main ADRs were diarrhea and vomiting. In prospective non-MDA studies, the most common toxicity was gastrointestinal ADRs (938/1967; 47.7%). The most serious toxicities were cardiac (prolonged QT or irregular heart beat) and idiopathic hypertrophic pyloric stenosis (IHPS). Compared with placebo, azithromycin did not show increased risk ADRs based on RCTs (risk difference − 0.17 to 0.07). The incidence of QT prolonged was higher in the medium-dosage group (10–30 mg/kg/day) than that of low-dosage group (≤ 10 mg/kg/day) (82.0% vs 1.2%). Conclusion The safety of azithromycin as MDA needs further evaluation. The most common ADRs are diarrhea and vomiting. The risk of the most serious uncommon ADRs (cardiac-prolonged QT and IHPS) is unknown.

Performance, kinetics characteristics and enhancement mechanisms in anammox process under Fe(II) enhanced conditions - Si-min Tang; Ze-hao Xu; Ya-lei Liu; Guang-feng Yang; Jun Mu; Ren-cun Jin; Qiao Yang; Xiao-ling Zhang (Biodegradation, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

An investigation of mass changes in the Bohai Sea observed by GRACE - Dapeng Mu; Tianhe Xu; Guochang Xu (Journal of Geodesy, 2020)
The Gravity Recovery and Climate Experiment (GRACE) satellite mission has profoundly advanced our knowledge of contemporary sea level change. Owing to the coarse spatial resolution and leakage issue across the land–ocean boundary, it is challenging (even impossible) for GRACE to detect mass changes over a region smaller than its spatial resolution, especially a semi-enclosed basin (e.g., the Bohai Sea) that is adjacent to land with significant mass variation. In this contribution, the causes for the GRACE RL06 mass changes in the Bohai Sea are investigated using a reconstruction technique that is implemented with multisource data, including altimeter observations, steric estimates, and land mass changes from GRACE RL06 mascon solution. Our results by the reconstruction technique demonstrate that the GRACE annual cycles are primarily caused by water mass changes rather than sediment changes. On the other hand, the mass trends from both reconstructed signals and those observed by the GRACE RL06 spherical harmonic coefficients (SHCs) are small, ranging from − 0.38 mm/year to 0.51 mm/year (depending on different data sources). Given that our estimated accuracies are > 0.8 mm/year (the real accuracies should be larger), our reconstructed results cannot directly confirm the presence of sediment accumulation or water mass increase; however, analysis of only the altimetry data suggests the mass trends are due to water mass increase, which would amount to ~ 0.44 Gt/year. Further investigation suggests that the mass trends in the Bohai Sea suffer from a − 2.9 mm/year leakage-in effect from groundwater depletion in the North China and about 2.5 mm/year signal attenuation (resulting in a ~ 2.5 mm/year remaining trend that is roughly equivalent to the leakage-in trend, consequently leading to the small mass trend in the Bohai Sea). Our reconstruction results exemplify that elaborate data processing is necessary for specific cases. We also test whether the recently released RL06 mascon solutions that are resolved with constraints and require no further processing would improve the agreement with altimeter observations. We find that the seasonal cycles are improved relative to the RL06 SHCs; however, the rates derived from the mascon solutions cannot properly represent the altimeter-derived ocean mass estimates for the Bohai Sea, probably because the mascon solutions underestimate the rates or contain some processing artifacts. Nevertheless, the mascon solutions show enhanced signals, which offer new opportunities to investigate regional sea level change.

Dual-Emitting N/S-Doped Carbon Dots-Based Ratiometric Fluorescent and Light Scattering Sensor for High Precision Detection of Fe(III) Ions - Zhiyan Chen; Xueqin Xu; Dongling Meng; Honglin Jiang; Yun Zhou; Shouai Feng; Zhao Mu; Yaling Yang (Journal of Fluorescence, 2020)

MiR-34a suppresses osteoblast differentiation through glycolysis inhibition by targeting lactate dehydrogenase-A (LDHA) - Mu Hong; Xiao-Bin Zhang; Fei Xiang; Xu Fei; Xue-Lian Ouyang; Xiao-Chun Peng (In Vitro Cellular & Developmental Biology - Animal, 2020)

Efficacy of fluopyram as a candidate trunk-injection agent against Bursaphelenchus xylophilus - Guangying Liu; Xu Lin; Shuangyu Xu; Guang Liu; Zhenyu Liu; Feng Liu; Wei Mu (European Journal of Plant Pathology, 2020)

Improved Arctic Ocean Mass Variability Inferred from Time-Variable Gravity with Constraints and Dual Leakage Correction - Dapeng Mu; Tianhe Xu; Guochang Xu (Marine Geodesy, 2020)

Recent advances in Levansucrase and Inulosucrase: evolution, characteristics, and application - Wei Xu; Dawei Ni; Wenli Zhang; Cuie Guang; Tao Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2019)

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

MicroRNA-532 exerts oncogenic functions in t(4;14) multiple myeloma by targeting CAMK2N1 - Kaihong Xu; Xuezhen Hu; Laifang Sun; Qingyue Liang; Guifang Ouyang; Yanli Zhang; Qitian Mu; Xiao Yan (Human Cell, 2019)

Comparative analysis of glucose metabolism responses of large yellow croaker Larimichthys crocea fed diet with fish oil and palm oil - Qi Wang; Hua Mu; Haohao Shen; Zhixiang Gu; Dong Liu; Mengxi Yang; Yue Zhang; Weiqi Xu; Wenbing Zhang; Kangsen Mai (Fish Physiology and Biochemistry, 2019)

Laboratory Experiments on an Internal Solitary Wave over a Triangular Barrier - Haidi Mu; Xu Chen; Qun Li (Journal of Ocean University of China, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

Influence of slab spatial composite effect on dynamic behaviour of composite frame structures under earthquake excitation - Xiao-Qiang Wang; Li-Yan Xu; Mu-Xuan Tao (Bulletin of Earthquake Engineering, 2019)

Experimental investigation on the optical remote sensing images of internal solitary waves with a smooth surface - Yuan Mei; Jing Wang; Songsong Huang; Haidi Mu; Xu Chen (Acta Oceanologica Sinica, 2019)

Fishery biology of whitespotted conger Conger myriaster (Brevoort, 1856) in the Yellow Sea and East China Sea - Xiuxia Mu; Chi Zhang; Ying Xue; Chongliang Zhang; Binduo Xu; Yiping Ren (Acta Oceanologica Sinica, 2019)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Models for temporal-spatial parameters in walking with cadence ratio as the independent variable - Juan Fang; Zaile Mu; Zhonghua Xu; Le Xie; Guo-Yuan Yang; Qiuju Zhang (Medical & Biological Engineering & Computing, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Association of polymorphisms of CYP11B2 gene –344C/T and ACE gene I/D with antihypertensive response to angiotensin receptor blockers in Chinese with hypertension - Hongtao Gong; Liying Mu; Tong Zhang; Xiuying Xu; Fenghe Du (Journal of Genetics, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Analysis of transcripts and splice isoforms in Medicago sativa L. by single-molecule long-read sequencing - Yuehui Chao; Jianbo Yuan; Tao Guo; Lixin Xu; Zhiyuan Mu; Liebao Han (Plant Molecular Biology, 2019)

Human activity during the late Pleistocene in the Lop Nur region, northwest China: Evidence from a buried stone artifact - Kangkang Li; Xiaoguang Qin; Xiaoyan Yang; Bing Xu; Lei Zhang; Guijin Mu; Dong Wei; Chunxue Wang; Yong Wu; Xiaohong Tian; Yongchong Lin; Wen Li; et al. (Science China Earth Sciences, 2018)

Comparative study of the physicochemical and photocatalytic properties of water-soluble polymer-capped TiO2 nanoparticles - Jinfeng Lei; Lei Deng; Xinying Li; Yongbin Xu; Defu Li; Changdao Mu (Environmental Science and Pollution Research, 2018)

Long non-coding RNA (lncRNA) MAGI2-AS3 inhibits breast cancer cell growth by targeting the Fas/FasL signalling pathway - Yong Yang; Hong Yang; Miao Xu; Haibin Zhang; Mingtao Sun; Peng Mu; Tongbao Dong; Shanmei Du; Kui Liu (Human Cell, 2018)

Spatial variation of the hypsometric integral and the implications for local base levels in the Yanhe River, China - Mingliang Luo; Yali Xu; Kai Mu; Rulan Wang; Yang Pu (Arabian Journal of Geosciences, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

Rapid identification of a major effect QTL conferring adult plant resistance to stripe rust in wheat cultivar Yaco“S” - Haiyang Li; Qilin Wang; Liangsheng Xu; Jingmei Mu; Jianhui Wu; Qingdong Zeng; Shizhou Yu; Lili Huang; Dejun Han; Zhensheng Kang (Euphytica, 2017)

Identification and validation of reference genes for gene expression studies in sweet osmanthus (Osmanthus fragrans) based on transcriptomic sequence data - Hongna Mu; Taoze Sun; Chen Xu; Lianggui Wang; Yuanzheng Yue; Huogen Li; Xiulian Yang (Journal of Genetics, 2017)

Chloride Co-transporter NKCC1 Inhibitor Bumetanide Enhances Neurogenesis and Behavioral Recovery in Rats After Experimental Stroke - Wangshu Xu; Xiaopeng Mu; Huibin Wang; Chengguang Song; Wenping Ma; Jukka Jolkkonen; Chuansheng Zhao (Molecular Neurobiology, 2017)

SIRT2-mediated FOXO3a deacetylation drives its nuclear translocation triggering FasL-induced cell apoptosis during renal ischemia reperfusion - Yan Wang; Yu Mu; Xiaorui Zhou; Huaixue Ji; Xing Gao; Wen Wen Cai; Qiuhua Guan; Tie Xu (Apoptosis, 2017)

Efficacy and safety of metformin and sitagliptin based triple antihyperglycemic therapy (STRATEGY): a multicenter, randomized, controlled, non-inferiority clinical trial - Wen Xu; Yiming Mu; Jiajun Zhao; Dalong Zhu; Qiuhe Ji; Zhiguang Zhou; Bin Yao; Anhua Mao; Samuel S. Engel; Bin Zhao; Yan Bi; Longyi Zeng; et al. (Science China Life Sciences, 2017)

Expression of SoxC Transcription Factors during Zebrafish Retinal and Optic Nerve Regeneration - Zhaoxia Mu; Shuqiang Zhang; Chunjiao He; Haitao Hou; Dong Liu; Nan Hu; Hui Xu (Neuroscience Bulletin, 2017)

Effects of intercropping tea with aromatic plants on population dynamics of arthropods in Chinese tea plantations - Zhengqun Zhang; Chao Zhou; Yongyu Xu; Xiaoqin Huang; Lixia Zhang; Wei Mu (Journal of Pest Science, 2017)

A new sesquiterpene from the South China Sea gorgonian coral Subergorgia suberosa - Mu-Wu Xu; Yuan-Tao Hao (Natural Product Research, 2016)

Non-integrating lentiviral vectors based on the minimal S/MAR sequence retain transgene expression in dividing cells - Zhen Xu; Feng Chen; Lingling Zhang; Jing Lu; Peng Xu; Guang Liu; Xuemin Xie; Wenli Mu; Yajun Wang; Depei Liu (Science China Life Sciences, 2016)

Propofol Prevents Hippocampal Neuronal Loss and Memory Impairment in Cerebral Ischemia Injury Through Promoting PTEN Degradation - Xin Chen; Ye-Mu Du; Feng Xu; Dai Liu; Yuan-Lin Wang (Journal of Molecular Neuroscience, 2016)

Recent research progress and prospects in tourism geography of China - Lin Lu; Jie Bao; Jianfeng Huang; Qijing Zhu; Chenglin Mu; Xiaole Chu; Yan Xu; Xiaoli Zha (Journal of Geographical Sciences, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

Oasis microclimate effect on the dust deposition in Cele Oasis at southern Tarim Basin, China - Lishuai Xu; Guijin Mu; Xiao Ren; Dejun Wan; Junxia He; Yongchong Lin (Arabian Journal of Geosciences, 2016)

Methyl jasmonate regulated diploid and tetraploid black locust (Robinia pseudoacacia L.) tolerance to salt stress - Mingquan Jiang; Fuling Xu; Mu Peng; Fenglan Huang; Fanjuan Meng (Acta Physiologiae Plantarum, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

Proanthocyanidin Protects Human Embryo Hepatocytes from Fluoride-Induced Oxidative Stress by Regulating Iron Metabolism - Qiang Niu; Lati Mu; Shugang Li; Shangzhi Xu; Ruling Ma; Shuxia Guo (Biological Trace Element Research, 2016)

Baseline sensitivity and efficacy of the sterol biosynthesis inhibitor triflumizole against Botrytis cinerea - Yingying Song; Datong Xu; Hongbao Lu; Leiming He; Lele Chen; Junan Shao; Chunmei Xu; Wei Mu; Feng Liu (Australasian Plant Pathology, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Characterization of the Aggregation-Induced Enhanced Emission of N,N′-bis(4-methoxysalicylide)benzene-1,4-diamine - Fuyong Wu; Guangjun Xu; Xi Zeng; Lan Mu; Carl Redshaw; Gang Wei (Journal of Fluorescence, 2015)

Desulfurization of immobilized sulfur-oxidizing bacteria, Thialkalivibrio versutus, by magnetic nanaoparticles under haloalkaliphilic conditions - Xiaohui Xu; Yufeng Cai; Ziyu Song; Xiaoling Qiu; Jiemin Zhou; Yilan Liu; Tingzhen Mu; Dan Wu; Yueping Guan; Jianmin Xing (Biotechnology Letters, 2015)

Isolation and detection of transcript-derived fragments (TDFs) in NaCl-stressed black locust (Robinia pseudoacacia L.) using cDNA-AFLP analysis - Fuling Xu; Mu Peng; Qiuxiang Luo; Mingquan Jiang; Xiuli Zhang; Xianchun Zong; Fanjuan Meng; Yajun Li (Acta Physiologiae Plantarum, 2015)

Enhanced lipid accumulation and biodiesel production by oleaginous Chlorella protothecoides under a structured heterotrophic-iron (II) induction strategy - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han (World Journal of Microbiology and Biotechnology, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Proteomics analysis for enhanced lipid accumulation in oleaginous Chlorella vulgaris under a heterotrophic-Na+ induction two-step regime - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han; Bo Feng; Hongyan Zeng (Biotechnology Letters, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Introducing a salt bridge into the lipase of Stenotrophomonas maltophilia results in a very large increase in thermal stability - Jian-Ping Wu; Mu Li; Yong Zhou; Li-Rong Yang; Gang Xu (Biotechnology Letters, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Attribution of maize yield increase in China to climate change and technological advancement between 1980 and 2010 - Jianping Guo; Junfang Zhao; Dingrong Wu; Jia Mu; Yanhong Xu (Journal of Meteorological Research, 2014)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

Bioremediation of endosulfan in laboratory-scale constructed wetlands: effect of bioaugmentation and biostimulation - Congcong Zhao; HuiJun Xie; Yang Mu; Xiaoli Xu; Jian Zhang; Cui Liu; Shuang Liang; Huu Hao Ngo; Wenshan Guo; Jingtao Xu; Qian Wang (Environmental Science and Pollution Research, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Molecular identification and interaction assay of the gene (OsUbc13) encoding a ubiquitin-conjugating enzyme in rice - Ya Wang; Meng-yun Xu; Jian-ping Liu; Mu-gui Wang; Hai-qing Yin; Ju-min Tu (Journal of Zhejiang University-SCIENCE B, 2014)

Scenario analysis on the adaptation of different maize varieties to future climate change in Northeast China - Yanhong Xu; Jianping Guo; Junfang Zhao; Jia Mu (Journal of Meteorological Research, 2014)

Seismic attenuation relationship with homogeneous and heterogeneous prediction-error variance models - He-Qing Mu; Rong-Rong Xu; Ka-Veng Yuen (Earthquake Engineering and Engineering Vibration, 2014)

Similarities between optimal precursors for ENSO events and optimally growing initial errors in El Niño predictions - Mu Mu; Yanshan Yu; Hui Xu; Tingting Gong (Theoretical and Applied Climatology, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

THE IMPACTS OF CLIMATE CHANGE ON WATER STRESS SITUATIONS IN THE YELLOW RIVER BASIN, CHINA - Jianxin Mu; Qunchang Liu; Hamza Farooq Gabriel; Di Xu; Jingdong Xu; Caili Wu; Hejing Ren (Irrigation and Drainage, 2013)
This paper used a back‐propagation (BP) neural network to conduct statistical downscaling based on the data (two factors: precipitation and temperature) downscaled by the National Climate Centre of China from over 20 global circulation models (GCMs) and input these downscaled data into the Basin‐wide Holistic Integrated Water Assessment (BHIWA) model to analyse irrigation water demand as well as water stress situations in both water quantity and quality in the Yellow River Basin, China. The results of the changes in climate in scenarios A1B, A2 and B1/B2 showed that irrigation water demand will increase and the water situation will become more stressed in 2030 and 2050, though there is still some increase in precipitation in most of the sub‐basins in these scenarios. Meanwhile, with the same variation range of precipitation and ET 0 , ET 0 will have a bigger impact on irrigation water demand and water stress situations than precipitation, This implies that ET 0 is a more dominant factor influencing water demand and water stress situations than other meteorological parameters such as precipitation. In addition to this, groundwater quality is more vulnerable to climate change than surface water quality and better water management will result in a decrease in irrigation water demand. Copyright © 2013 John Wiley & Sons, Ltd.

A STOCHASTIC APPROACH TO ANALYSE WATER MANAGEMENT SCENARIOS AT THE RIVER BASIN LEVEL - Jianxin Mu; Shahbaz Khan; Qunchang Liu; Di Xu; Jingdong Xu; Wenhao Wang (Irrigation and Drainage, 2013)
Quantitative analysis techniques have gained a great deal of popularity with decision‐makers and analysts in recent years, and this is also the case in the hydrology sector. In this paper, the Basin‐wide Holistic Integrated Water Assessment (BHIWA) model developed by the International Commission on Irrigation and Drainage (ICID) was updated by the author to simulate the water balance of the Yellow River Basin in China, as well as to analyse the impacts of land and water use on return flows of this basin under past (1980), present (2000), and future (2030 and 2050) conditions. Stochastic analysis was then carried out using the Monte Carlo simulation method, by randomly selecting sets of values for the probability distributions in the cell values and formulas to quantify the risks in terms of water quantity and quality resulting from return flow. The model amply demonstrates the serious water shortage situation in the future. Developing the strategy of water‐saving measures would greatly enhance the efficiency of irrigation water use, and decrease water withdrawal for irrigation. In addition to this, a possible opportunity to transfer water from the Yangtze River to the Yellow River also came to light. Copyright © 2013 John Wiley & Sons, Ltd.

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Genetic diversity of two Tibetan macaque (Macaca thibetana) populations from Guizhou and Yunnan in China based on mitochondrial DNA D-loop sequences - Li-Jing Zhong; Ming-Wang Zhang; Yong-Fang Yao; Qing-Yong Ni; Jun Mu; Chong-Qing Li; Huai-Liang Xu (Genes & Genomics, 2013)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

NUMERICAL SIMULATIONS AND VALIDATION OF WATER FLOW AND HEAT TRANSPORT IN A SUBSURFACE DRIP IRRIGATION SYSTEM USING HYDRUS‐2D - Jiandong Wang; Shihong Gong; Di Xu; Sui Juan; Jianxin Mu (Irrigation and Drainage, 2013)
Subsurface drip irrigation (SDI) systems are often recommended to overcome water scarcity in arid and semi‐arid regions. To properly manage SDI systems, precise prediction of distribution and transport of soil water content and temperature (important soil physical factors for plant growth) around the emitters must be known. In this paper, the computer software package HYDRUS‐2D was used to evaluate the distribution and transport of soil water content and temperature around an emitter in a silt loam soil. The model was validated by comparison with measured data from field experiments involving SDI with emitters installed at 25‐cm soil depths. Model performance in simulating soil moisture and temperature was evaluated by comparing measured and predicted values using three parameters: model efficiency (ME), root mean square deviation (RMSE) and mean bias error (MBE). Values of ME, RMSE and MBE between measured and simulated soil moisture ranged from 0.71 to 0.84, 0.013 to 0.019 and 0.004 to 0.007 and between measured and simulated soil temperature ranged from 0.81 to 0.86, 0.97 to 1.33 and 0.13 to 0.28, respectively. Based on these values, it can be concluded that there was good correspondence between simulations and observations and the HYDRUS‐2D can be commendably used to describe soil water and heat transport properties involving SDI and also for investigating and designing drip irrigation management practices. Copyright © 2013 John Wiley & Sons, Ltd.

Participatory agroforestry development for restoring degraded sloping land in DPR Korea - Jianchu Xu; Meine van Noordwijk; Jun He; Kwang-Ju Kim; Ryong-Song Jo; Kon-Gyu Pak; Un-Hui Kye; Jong-Sik Kim; Kwon-Mu Kim; Yong-Nam Sim; Je-Un Pak; Ki-Ung Song; et al. (Agroforestry Systems, 2012)

De novo characterization of the root transcriptome of a traditional Chinese medicinal plant Polygonum cuspidatum - DaCheng Hao; Pei Ma; Jun Mu; ShiLin Chen; PeiGen Xiao; Yong Peng; Li Huo; LiJia Xu; Chao Sun (Science China Life Sciences, 2012)

Molecular cloning, characterization, and function analysis of a mevalonate pyrophosphate decarboxylase gene from Ganoderma lucidum - Liang Shi; Lei Qin; Yingjie Xu; Ang Ren; Xing Fang; Dashuai Mu; Qi Tan; Mingwen Zhao (Molecular Biology Reports, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

An approach to the study of copepod egg banks based on efficient DNA extraction from individual copepod eggs - Zhi-Huan Xu; Gui-Zhong Wang; Qian Mu; Li-Sheng Wu; Shao-Jing Li (Marine Biology Research, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Immune response to fused core protein of hepatitis C virus and truncated tetanus toxin peptides in mice - Xing-bin Hu; Qiao-hong Yue; Hai-feng Ouyang; Yao-zhen Chen; Xue-qing Xu; Wen Yin; San-hua Wei; Xian-qing Zhang; Shi-jie Mu (Archives of Virology, 2010)

Interaction between aluminum toxicity and manganese toxicity in soybean (Glycine max) - Zhong Bao Yang; Jiang Feng You; Mu Yun Xu; Zhen Ming Yang (Plant and Soil, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Microbial production of 1,3-propanediol from glycerol by Klebsiella pneumoniae under micro-aerobic conditions up to a pilot scale - Hai-Jun Liu; Dai-Jia Zhang; You-Hai Xu; Ying Mu; Ya-Qin Sun; Zhi-Long Xiu (Biotechnology Letters, 2007)

Applications of conditional nonlinear optimal perturbation in predictability study and sensitivity analysis of weather and climate - Mu Mu; Wansuo Duan; Hui Xu; Bo Wang (Advances in Atmospheric Sciences, 2006)

High-yield conversion of (R)-2-octanol from the corresponding racemate by stereoinversion using Candida rugosa - Yao Nie; Yan Xu; Xiao Qing Mu; Yan Tang; Juan Jiang; Zhi Hao Sun (Biotechnology Letters, 2005)

Molecular marker application in sugarcane - Mu-Qing Zhang; Xue-Fang Zheng; Ai-Li Yu; Jing-Sheng Xu; Hui Zhou (Sugar Tech, 2004)

A spatial cluster method supported by GIS for urban-suburban-rural classification - De-min Zhou; Jian-chun Xu; John Radke; Lan Mu (Chinese Geographical Science, 2004)